Precursor glasses and glass-ceramics containing a crystalline phase having the jeffvenite crystal structure

JP2025506109APending Publication Date: 2025-03-07CORNING INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024545127
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-08-12
Filing Date
2023-02-13
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0007】 さらに、ここに記載されたガラスセラミックは、優れた硬度値と剛性値を達成し、したがって、薄く軽量の携帯電話およびタブレットのディスプレイ面を可能にすることができる。同じ特徴により、電話とタブレットの筐体用の不透明または着色ガラスセラミックが可能になる。さらに、これらのガラスセラミックは、リチウムを含まず、それでも、イオン交換による強化に適しており、この十分ではない資源の必要性を低下させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025506109000001_ABST
    Figure 2025506109000001_ABST
Patent Text Reader

Abstract

Disclosed herein is a glass-ceramic article comprising a crystalline phase having a jehvenite crystal structure. The glass-ceramic article may have a first surface, a second surface opposite the first surface, and a periphery defining the shape of the glass-ceramic article. The glass-ceramic article may further comprise a phase assemblage comprising one or more crystalline phases and a glass phase. The one or more crystalline phases may include a crystalline phase having a jehvenite crystal structure.
Need to check novelty before this filing date? Find Prior Art

Description

Description of Related Applications

[0001] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 309,667, filed February 14, 2022, entitled "Precursor Glasses and Glass-Ceramics Comprising a Crystalline Phase having a Jeffbenite Crystalline Structure," and U.S. Patent Application No. 17 / 887,012, filed August 12, 2022, entitled "Precursor Glasses and Glass-Ceramics Comprising a Crystalline Phase having a Jeffbenite Crystalline Structure," all of which are incorporated herein by reference. [Technical field]

[0002] This specification relates to precursor glasses and glass-ceramic articles made therefrom. [Background technology]

[0003] Both consumer and commercial electronic devices, such as smartphones, tablets, portable media players, personal computers, and cameras, utilize glass articles, such as cover glass, glass backplanes, and housings. The portable nature of these portable devices makes them, and the glass articles contained therein, particularly susceptible to being accidentally dropped onto hard surfaces, such as the ground. Additionally, glass articles, such as cover glass, may be provided with "touch" capabilities, which entails that the glass article be touched by various objects, including a user's finger and / or stylus instrument. Thus, glass articles must be robust enough to withstand accidental drops and everyday contact without scratches or other damage. In fact, scratches introduced into the surface of a glass article will reduce the strength of the glass article, as they may act as initiation points for cracks that lead to catastrophic breakage of the glass. Summary of the Invention [Problem to be solved by the invention]

[0004] Therefore, there is a need for alternative materials that have improved mechanical properties compared to glass. [Means for solving the problem]

[0005] Features and advantages of the precursor glasses and glass-ceramics described herein are set forth in the following detailed description, and in part will be readily apparent to those skilled in the art from that description, or may be learned by practicing the embodiments described herein, including the following detailed description, claims, and accompanying drawings.

[0006] Applicants have discovered that the jeffbenite crystal structure associated with inclusions in "super deep origin" diamonds, when formed in glass as a crystalline phase in a glass-ceramic, as described herein, may provide many useful advantages and properties. Applicants believe that a crystalline phase having the jeffbenite crystal structure has not previously been grown or otherwise formed in a glass-ceramic. Applicants further believe that a crystalline phase having the jeffbenite crystal structure has not previously been formed or otherwise incorporated into a glass-ceramic article, such as a glass-ceramic sheet, glass-ceramic container, window, panel, housing, plate, countertop, utensil, bar, fiber, or other such article. Furthermore, in contrast to jeffvenite in (anisotropic) diamond or isolated, applicants believe that a crystalline phase having jeffvenite crystal structure has not previously been included in an article having isotropic material properties (e.g., properties such as tensile strength, elasticity, and fracture toughness that remain the same when tested in different directions) as effectively achieved by the inclusion of relatively small randomly oriented and uniformly distributed crystal grains, as disclosed herein, within a residual glass or within another isotropic solid medium (e.g., a polymer) to form a glass-ceramic. Applicants believe that a glass-ceramic comprising a crystalline phase having jeffvenite crystal structure has not previously been in fact manufactured; grown from a precursor glass; or formed at temperatures (e.g., <1600K, <1400K) and pressures (e.g., <12GPa, e.g., <10GPa, <8GPa, <1GPa, e.g., even 1 atmosphere (about 101Pa)) as disclosed herein. As a result of this discovery, large quantities of crystals with the jeffvenite crystal structure can now be produced in a single batch, in part because the extreme temperatures and pressures associated with their formation super-deep within the Earth's mantle are not required.

[0007] Additionally, the glass-ceramics described herein achieve excellent hardness and stiffness values, thus enabling thin, lightweight cell phone and tablet display surfaces. The same characteristics enable opaque or colored glass-ceramics for phone and tablet housings. Additionally, these glass-ceramics do not contain lithium, yet are suitable for strengthening by ion exchange, reducing the need for this scarce resource.

[0008] Embodiment 1 comprises a glass-ceramic article comprising: a first surface; a second surface opposite the first surface; a periphery defining a shape of the glass-ceramic article; and a phase assemblage comprising one or more crystalline phases and a glassy phase, wherein the one or more crystalline phases have a jeffvenite crystal structure.

[0009] Example 2 includes the glass-ceramic article of example 1, wherein the one or more crystalline phases having a jeffvenite crystal structure are a predominant crystalline phase.

[0010] Aspect 3 is a method for preparing a crystalline matrix having one or more crystalline phases having a crystalline structure represented by the formula: (Mg,R 2+ ) 3+x (Zr,R 4+ ) x Al 2-2x SiO 12 wherein R 2+ is a divalent metal cation, and R 4+ is a tetravalent metal cation and x is greater than or equal to 0 and less than 1.

[0011] Aspect 4 is a method for producing a crystalline phase having a zirconia crystal structure represented by the formula: (Mg,R 2+ ) 3+x (Zr,R 4+ ) x Al 2-2x SiO 12 wherein R 2+ is a divalent metal cation, and R 4+is a tetravalent metal cation and x is from 0 to 1, inclusive.

[0012] Aspect 5 is R 2+ But, Ca 2+ , Mn 2+ , Fe 2+ and R is one or more divalent metal cations selected from 4+ But, Ti 4+ , Sn 4+ , Hf 4+ The glass-ceramic article of embodiment 4, wherein the one or more tetravalent metal cations are selected from:

[0013] Aspect 6 is directed to a method for producing a crystalline zirconia composition comprising the steps of: (Mg,Fe,Mn,Zn) 3+x (Zr, Ti, Sn) x Al 2-2x SiO 12 wherein x is greater than or equal to 0 and less than 1.

[0014] Aspect 7 is directed to a method for preparing a crystalline matrix comprising the step of: 3+x Zr x Al 2-2x SiO 12 wherein x is greater than or equal to 0 and less than 1.

[0015] Example 8 includes the glass-ceramic article of any previous example, wherein the one or more crystalline phases include one or more minor crystalline phases.

[0016] Example 9 includes the glass-ceramic article of example 8, wherein the one or more minor crystalline phases comprises a ZrO 2 crystalline phase.

[0017] Example 10 includes the glass-ceramic article of example 8, wherein the one or more minor crystalline phases include a ZrTiO 4 crystalline phase.

[0018] Example 11 includes the glass-ceramic article of any previous example, wherein the phase assemblage includes 25% by weight or more of one or more crystalline phases and 75% by weight or less of a glass phase.

[0019] Example 12 includes the glass-ceramic article of any previous example, wherein at least some particles of at least one crystalline phase having a jeffvenite crystal structure have dimensions from 20 nm or more to 100 nm or less.

[0020] Example 13 includes the glass-ceramic article of any previous example, wherein the glass-ceramic article has an average transmittance of at least 75% for light in the wavelength range of 400 nm to 800 nm at an article thickness of 0.6 mm.

[0021] Example 14 includes the glass-ceramic article of Examples 1-12, wherein the glass-ceramic article has an average transmittance in the range of from 20% to less than 75% for light in the wavelength range of 400 nm to 800 nm at an article thickness of 0.6 mm.

[0022] Example 15 includes the glass-ceramic article of Examples 1-12, wherein the glass-ceramic article has an average transmittance for light in the wavelength range of 400 nm to 800 nm at an article thickness of 0.6 mm in a range of less than 20%.

[0023] Example 16 includes the glass-ceramic article of any previous example, comprising 35 mol% to 65 mol% SiO, 5 mol% to 20 mol% AlO, 10 mol% to 45 mol% MgO, 1 mol% to 7 mol% ZrO, 0 mol% to 15 mol% NaO, 0 mol% to 15 mol% KO, 0 mol% to 9 mol% FeO, 0 mol% to 1 mol% MnO, and 0 mol% to 12 mol% ZnO.

[0024] Example 17 includes the glass-ceramic article of Examples 1-15, wherein the glass-ceramic comprises from about 35 mol% to about 65 mol% SiO, from about 5 mol% to about 20 mol% AlO, from about 7 mol% to about 65 mol% MgO, from about 0 mol% to about 7 mol% ZrO, from about 0 mol% to about 15 mol% NaO, from about 0 mol% to about 15 mol% KO, from about 0 mol% to about 9 mol% FeO, from about 0 mol% to about 10 mol% MnO, and from about 0 mol% to about 15 mol% ZnO, wherein the glass-ceramic comprises a phase assemblage comprising one or more crystalline phases and a glassy phase, wherein the one or more crystalline phases comprises a crystalline phase having a jeffvenite crystal structure.

[0025] Example 18 includes the glass-ceramic article of any previous example, comprising greater than or equal to 48 mol % and less than or equal to 54 mol % SiO.

[0026] Example 19 includes the glass-ceramic article of any previous example, comprising greater than or equal to 9 mol % and less than or equal to 13 mol % Al2O3.

[0027] Example 20 includes the glass-ceramic article of any previous example, comprising greater than or equal to 1 mol % and less than or equal to 15 mol % Na2O.

[0028] Example 21 includes the glass-ceramic article of any previous example, comprising greater than or equal to 1 mol % and less than or equal to 15 mol % KO.

[0029] Example 22 includes the glass-ceramic article of any previous example, wherein NaO(mol%) + KO(mol%) is greater than or equal to 2 mol% and less than or equal to 15 mol%.

[0030] Example 23 includes the glass-ceramic article of any previous example, wherein Na2O(mol%) / (Na2O(mol%)+K2O(mol%)) is 0.3 or greater.

[0031] Example 24 includes the glass-ceramic article of Examples 1-22, wherein Na2O(mol %) / (Na2O(mol %)+K2O(mol %)) is 0.2 or greater.

[0032] Example 25 includes the glass-ceramic article of any previous example, further including, greater than or equal to 0.3 mol % and less than or equal to 7 mol % TiO2.

[0033] Example 26 includes the glass-ceramic article of any previous example, wherein ZrO2 (mol %) + TiO2 (mol %) is 2 mol % or greater.

[0034] Example 27 includes the glass-ceramic article of any previous example, wherein ZrO2(mol%) / (ZrO2(mol%)+TiO2(mol%)) is 0.3 or greater.

[0035] Example 28 includes the glass-ceramic article of any previous example, comprising greater than or equal to 1 mol % and less than or equal to 12 mol % ZnO.

[0036] Example 29 includes the glass-ceramic article of any previous example, further including up to 3 mol % LiO2.

[0037] Example 30 includes the glass-ceramic article of any previous example, wherein the glass-ceramic article is substantially free of LiO.

[0038] Example 31 includes the glass-ceramic article of any previous example, further including, greater than or equal to 1 mol % and less than or equal to 8 mol % BaO.

[0039] Example 32 includes the glass-ceramic article of any previous example, further including, from greater than or equal to 0.2 mol % to less than or equal to 1.7 mol % of at least one of CaO and SrO.

[0040] Example 33 includes the glass-ceramic article of any previous example, wherein the glass-ceramic article is substantially free of P2O5.

[0041] Example 34 includes the glass-ceramic article of Examples 1-32, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 4 mol % P2O5.

[0042] Example 35 includes the glass-ceramic article of any previous example, wherein the glass-ceramic article includes, from greater than or equal to 1.5 mol % to less than or equal to 3 mol % ZrO2.

[0043] Example 36 includes the glass-ceramic article of any previous example, wherein the glass-ceramic article comprises from greater than 0 mol % to less than or equal to 12 mol % HfO2, and the sum of ZrO2 and HfO2 is greater than 1 mol %.

[0044] Example 37 includes the glass-ceramic article of any previous example, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 15 mol % CaO.

[0045] Example 38 includes the glass-ceramic article of any previous example, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 7 mol % La2O3.

[0046] Embodiment 39 includes a glass-ceramic article that includes 35 mol% to 65 mol% SiO, 5 mol% to 20 mol% AlO, 10 mol% to 45 mol% MgO, 1 mol% to 7 mol% ZrO, 0 mol% to 15 mol% NaO, 0 mol% to 15 mol% KO, 0 mol% to 9 mol% FeO, 0 mol% to 1 mol% MnO, and 0 mol% to 12 mol% ZnO, wherein the glass-ceramic article includes a glass phase and a crystalline phase having a jeffvenite crystal structure.

[0047] Embodiment 40 includes a glass-ceramic article comprising 35 mol% to 65 mol% SiO, 5 mol% to 20 mol% AlO, 7 mol% to 65 mol% MgO, 0 mol% to 7 mol% ZrO, 0 mol% to 15 mol% NaO, 0 mol% to 15 mol% KO, 0 mol% to 9 mol% FeO, 0 mol% to 10 mol% MnO, and 0 mol% to 15 mol% ZnO, wherein the glass-ceramic article comprises a glass phase and a crystalline phase having a jeffvenite crystal structure.

[0048] Aspect 41 is a method for producing a crystalline phase having a jeffvenite crystal structure, the crystalline phase being represented by the formula: (Mg,R 2+ ) 3+x (Zr,R 4+ ) x Al 2-2x SiO 12 wherein R 2+ is a divalent metal cation, and R 4+ is a tetravalent metal cation and x is greater than or equal to 0 and less than 1.

[0049] Aspect 42 is a method for producing a crystalline phase having a jeffvenite crystal structure, the crystalline phase being represented by the formula: (Mg,R 2+ ) 3+x (Zr,R 4+ ) x Al 2-2x SiO 12 wherein R 2+ is a divalent metal cation, and R 4+ is a tetravalent metal cation and x is from 0 to 1, inclusive.

[0050] Aspect 43 is R 2+ But, Ca 2+ , Mn 2+ , Fe 2+ and R is one or more divalent metal cations selected from 4+ But, Ti 4+ , Sn 4+ , Hf 4+ The glass-ceramic article of embodiment 42, wherein the one or more tetravalent metal cations are selected from:

[0051] Embodiment 44 is a method for producing a crystalline phase having a jeffvenite crystal structure, the crystalline phase having the formula: (Mg,Fe,Mn,Zn) 3+x (Zr, Ti, Sn) x Al 2-2x SiO 12 wherein x is greater than or equal to 0 and less than 1.

[0052] Embodiment 45 is directed to a method for preparing a crystalline phase having a jeffvenite crystal structure, the crystalline phase having the formula: Mg 3+x Zr x Al 2-2x SiO 12 wherein x is greater than or equal to 0 and less than 1.

[0053] Example 46 includes the glass-ceramic article of Examples 39-45, wherein a crystalline phase having a jeffvenite crystal structure is a predominant crystalline phase.

[0054] Example 47 includes the glass-ceramic article of Examples 39-46, comprising from greater than or equal to 48 mol % to less than or equal to 54 mol % SiO2.

[0055] Example 48 includes the glass-ceramic article of any of Examples 39-47, comprising greater than or equal to 9 mol % and less than or equal to 13 mol % Al2O3.

[0056] Example 49 includes the glass-ceramic article of any of Examples 39-48, comprising greater than or equal to 1 mol % and less than or equal to 15 mol % Na2O.

[0057] Example 50 includes the glass-ceramic article of Examples 39-49, comprising greater than or equal to 2 mol % and less than or equal to 5 mol % Na2O.

[0058] Example 51 includes the glass-ceramic article of Examples 39-50, comprising greater than or equal to 1 mol % and less than or equal to 15 mol % K2O.

[0059] Example 52 includes the glass-ceramic article of Examples 39-51, comprising greater than or equal to 1 mol % and less than or equal to 5 mol % K2O.

[0060] Example 53 includes the glass-ceramic article of any of Examples 39-52, wherein Na2O(mol %) + K2O(mol %) is from 2 mol % or more to 15 mol % or less.

[0061] Example 54 includes the glass-ceramic article of any of Examples 39-53, wherein Na2O(mol %) / (Na2O(mol %)+K2O(mol %)) is 0.3 or greater.

[0062] Example 55 includes the glass-ceramic article of any of Examples 39-53, wherein Na2O(mol %) / (Na2O(mol %)+K2O(mol %)) is 0.2 or greater.

[0063] Example 56 includes the glass-ceramic article of any of Examples 39-55, further comprising greater than or equal to 0.3 mol % and less than or equal to 7 mol % TiO2.

[0064] Example 57 includes the glass-ceramic article of any of Examples 39-56, wherein ZrO2 (mol %) + TiO2 (mol %) is 2 mol % or greater.

[0065] Example 58 includes the glass-ceramic article of any of Examples 39-57, wherein ZrO2(mol %) / (ZrO2(mol %)+TiO2(mol %)) is 0.3 or greater.

[0066] Example 59 includes the glass-ceramic article of any of Examples 39-58, comprising from greater than or equal to 1 mol % to less than or equal to 12 mol % ZnO.

[0067] Example 60 includes the glass-ceramic article of any of Examples 39-59, further including up to 3 mol % LiO2.

[0068] Example 61 includes the glass-ceramic article of any of Examples 39-60, wherein the glass-ceramic article is substantially free of LiO2.

[0069] Example 62 includes the glass-ceramic article of Examples 39-61, further including greater than or equal to 1 mol % and less than or equal to 8 mol % BaO.

[0070] Example 63 includes the glass-ceramic article of any of Examples 39-62, further including greater than or equal to 0.2 mol % and less than or equal to 1.7 mol % of at least one of CaO and SrO.

[0071] Example 64 includes the glass-ceramic article of any of Examples 39-63, wherein the glass-ceramic article is substantially free of P2O5.

[0072] Example 65 includes the glass-ceramic article of any of Examples 39-63, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 4 mol % P2O5.

[0073] Example 66 includes the glass-ceramic article of any of Examples 39-65, wherein the glass-ceramic article includes greater than or equal to 1.5 mol % and less than or equal to 3 mol % ZrO2.

[0074] Example 67 includes the glass-ceramic article of any of Examples 39-66, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 7 mol % HfO2.

[0075] Example 68 includes the glass-ceramic article of any of Examples 39-67, wherein the glass-ceramic article comprises from greater than 0 mol % to less than or equal to 15 mol % CaO.

[0076] Example 69 includes the glass-ceramic article of any of Examples 39-68, wherein the glass-ceramic article comprises from greater than 0 mol % to less than or equal to 7 mol % La2O3.

[0077] Embodiment 70 is directed to a glass-ceramic article having a hardness of 2.65 g / cm 3 From the above, 2.95g / cm 3 The glass-ceramic articles of embodiments 39-69 have the following densities:

[0078] Embodiment 71 is directed to a glass-ceramic article having a hardness of 2.50 g / cm 3 From the above, 3.70g / cm 3 The glass-ceramic articles of embodiments 39-69 have the following densities:

[0079] Example 72 includes the glass-ceramic article of Examples 39-71, further including a ZrO 2 crystalline phase.

[0080] Example 73 includes the glass-ceramic article of Examples 39-72, further including a ZrTiO 4 crystalline phase.

[0081] Example 74 includes the glass-ceramic article of Examples 39-73, wherein at least some particles of the crystalline phase having the jeffvenite crystal structure have dimensions from 20 nm or more to 100 nm or less.

[0082] Example 75 includes a consumer electronic device comprising: a housing having a front, a back, and sides; electrical components at least partially disposed within the housing, the electrical components including at least a controller, a memory, and a display at or adjacent to the front of the housing; and at least one of the glass-ceramic article of any previous example disposed over the display and forming a part of the housing.

[0083] Example 76 includes a method of making a glass-ceramic article, comprising: heat treating a precursor glass including SiO, AlO, MgO, and ZnO to nucleate one or more crystalline phases in the precursor glass, the one or more crystalline phases having a jeffvenite crystal structure, the precursor glass optionally including one or more of FeO, MnO, and ZnO; and growing the one or more crystalline phases within the glass phase.

[0084] Example 77 includes a method of making a glass-ceramic article, comprising: heat treating a precursor glass including SiO, AlO, and MgO to nucleate one or more crystalline phases in the precursor glass, wherein the one or more crystalline phases have a jeffvenite crystal structure; and growing the one or more crystalline phases within the glass phase.

[0085] Example 78 includes the method of making the glass-ceramic article of example 76 or 77, wherein the heat treating step includes heating the precursor glass to a first temperature of greater than or equal to 700° C. and less than or equal to 950° C. and maintaining the precursor glass at the first temperature for a first period of time of greater than or equal to 0.25 hours and less than or equal to 6 hours.

[0086] Example 79 includes the method of making the glass-ceramic article of example 78, wherein the heat treating step includes heating the precursor glass to a second temperature of greater than or equal to 750° C. and less than or equal to 950° C. and maintaining the precursor glass at the second temperature for a second period of time of greater than or equal to 0.25 hours and less than or equal to 6 hours.

[0087] Example 80 includes a method of making the glass-ceramic article of Examples 76-79, wherein a crystalline phase having a jeffvenite crystal structure is a predominant crystalline phase.

[0088] Embodiment 81 is a method for preparing a crystalline phase having a structure represented by the formula: (Mg,R 2+ ) 3+x (Zr,R 4+ ) x Al 2-2x SiO 12 wherein x is greater than or equal to 0 and less than 1.

[0089] Embodiment 82 is directed to a method for preparing a crystalline phase having a jeffvenite crystal structure, the crystalline phase having the formula: (Mg,R 2+ ) 3+x (Zr,R 4+ ) x Al 2-2x SiO 12 wherein x is from 0 to 1, inclusive.

[0090] Embodiment 83 is directed to a method for preparing a crystalline phase of a zirconia alloy having the formula: (Mg,Fe,Mn,Zn) 3+x (Zr, Ti, Sn) x Al 2-2x SiO 12 wherein x is greater than or equal to 0 and less than 1.

[0091] Embodiment 84 is a method for preparing a crystalline phase having the formula: Mg 3+x Zr x Al 2-2x SiO 12wherein x is greater than or equal to 0 and less than 1.

[0092] Example 85 includes a method of making the glass-ceramic article of Examples 76-84, wherein the glass-ceramic article includes a phase assemblage that includes one or more crystalline phases and a glassy phase.

[0093] Example 86 includes a method of making the glass-ceramic article of example 85, wherein the one or more crystalline phases include one or more minor crystalline phases.

[0094] Example 87 includes a method of making the glass-ceramic article of example 86, wherein the one or more minor crystalline phases include ZrO.

[0095] Example 88 includes a method of making the glass-ceramic article of example 86, wherein the one or more minor crystalline phases include ZrTiO.

[0096] Example 89 includes a method of making the glass-ceramic article of Examples 85-88, wherein the phase assemblage includes 25% by weight or more of one or more crystalline phases and 75% by weight or less of a glass phase.

[0097] Example 90 includes a method of making the glass-ceramic article of Examples 85-89, wherein at least some particles of the crystalline phase having the jeffvenite crystal structure have dimensions from 20 nm or more to 100 nm or less.

[0098]

[0023] Embodiment 91 includes a glass-ceramic article having a first major surface and a second major surface facing away from the first major surface, an edge forming an outer periphery of the first and second major surfaces and extending between the first and second major surfaces, and a body between the first and second major surfaces and the edge, the body being made from a glass ceramic including a crystalline phase having a jeffvenite crystal structure, wherein a thickness of the article is defined as the distance between the first and second major surfaces, a width of the article is defined as the distance between the edges along the first major surface perpendicular to the thickness, and a length of the article is defined as the distance between the edges along the first major surface perpendicular to both the width and the thickness, and wherein the width is greater than or equal to the thickness and the length is greater than or equal to the width.

[0099] Example 92 includes the glass-ceramic article of example 91, wherein the glass-ceramic article comprises a glass-ceramic sheet.

[0100] Example 93 includes the glass-ceramic article of example 91 or example 92, wherein particles of a crystalline phase having a jeffvenite crystal structure are uniformly distributed throughout the glass-ceramic body.

[0101] Example 94 includes the glass-ceramic article of Examples 91-93, wherein grains of a crystalline phase having a jeffvenite crystal structure are randomly oriented within the body glass-ceramic.

[0102] In accordance with embodiment 95, particles of a crystalline phase having a jeffvenite crystal structure are formed within the body glass-ceramic, the fracture toughness of which is greater than or equal to 0.75 MPa m 1 / 2 The glass-ceramic articles of any of embodiments 91-94, which overlap and interlock with each other to any degree.

[0103] Example 96 includes the glass-ceramic article of Examples 91-95, wherein the glass-ceramic has isotropic material properties.

[0104] Example 97 includes the glass-ceramic article of Examples 91-96, wherein the thickness is greater than or equal to 200 μm and less than or equal to 5 mm.

[0105] Example 98 includes the glass-ceramic article of Examples 91-97, wherein both the length and width are greater than 5 mm.

[0106] In embodiment 99, the first major surface is 25 mm 2 The glass-ceramic article of any one of embodiments 91 to 98, having an area of ​​at least 100 mm or more.

[0107] The embodiment 100 has a volume of glass ceramic within the body of 25 mm 3 The above includes glass-ceramic articles of embodiments 91 to 99.

[0108] Example 101 includes the glass-ceramic article of Examples 91-100, wherein the body consists essentially of a glass-ceramic and is at least partially translucent such that at least 20% of light having a wavelength of 400 to 800 nanometers directed into the thickness of the article is transmitted through the body.

[0109] Embodiment 102 includes a method of making a glass ceramic comprising: heat treating a precursor glass including nucleation sites to grow particles of a crystalline phase having a javenite crystal structure from the nucleation sites in the precursor glass to form a glass ceramic including a crystalline phase having a javenite crystal structure and residual glass; and growing particles of the crystalline phase having a javenite crystal structure during the heat treatment such that at least some of the particles of the crystalline phase having the javenite crystal structure have dimensions of 20 nm or greater.

[0110] Example 103 includes the method of Example 102, wherein the growing step occurs at atmospheric pressure.

[0111] Example 104 includes the methods of Examples 102-103, wherein the temperature of the precursor glass during the heat treatment remains below 1500 K throughout the heat treatment.

[0112] Example 105 includes the method of Examples 102-104, wherein after the growing step, at least some of the particles of the crystalline phase having the jeffvenite crystal structure overlap and interdigitate with one another within the residual glass of the glass-ceramic.

[0113] Example 106 includes the methods of Examples 102-105, wherein after the growing step, at least some of the particles of the crystalline phase having the jeffvenite crystal structure have dimensions less than or equal to 5 μm.

[0114] Example 107 includes the methods of Examples 102-106, wherein the nucleation sites are positioned within the precursor glass such that particles of a crystalline phase having a jeffvenite crystal structure are uniformly distributed within the glass-ceramic.

[0115] Example 108 includes the method of Examples 102-107, wherein the heat treating is such that grains of a crystalline phase having a jeffvenite crystal structure grow throughout the glass-ceramic.

[0116] Example 109 includes the methods of Examples 102-108, wherein grains of a crystalline phase having a jeffvenite crystal structure are grown with random orientation relative to one another and are dispersed within the residual glass of the glass-ceramic.

[0117] Example 110 includes the methods of Examples 102-109, wherein a crystalline phase having a jeffvenite crystal structure is a predominant crystalline phase of the glass-ceramic.

[0118] Example 111 includes the methods of Examples 102-110, wherein after the growing step, the glass-ceramic has isotropic material properties.

[0119] Embodiment 112 includes a glass-ceramic article comprising: crystals of pyrope-almandine garnet stoichiometry having a tetragonal structure in a glass-ceramic article; and an amorphous glass surrounding and encapsulating the crystals such that the crystals and glass together form the glass ceramic of the glass-ceramic article.

[0120] Example 113 includes the glass-ceramic article of Example 112, wherein the tetragonal structure falls within the I-42d space group.

[0121] Embodiment 114 includes a glass-ceramic article having an "a" lattice parameter greater than or equal to 6.5 Å and less than or equal to 6.7 Å; a "c" lattice parameter greater than or equal to 18.0 Å and less than or equal to 18.5 Å; and an X-ray diffraction spectrum having a first peak between 2θ angles of 30° to 32°, a second peak between 2θ angles of 33° to 35°, a third peak between 2θ angles of 40° to 42°, and a fourth and fifth peak between 2θ angles of 55° to 58°, where the first, second, third, fourth, and fifth peaks correspond to jeffvenite.

[0122] Embodiment 115 includes a glass-ceramic that includes jeffvenite.

[0123]

[0041] Example 116 includes an article having: a surface; and a body within the surface, the body being made from the glass-ceramic of Example 115.

[0124] Embodiment 117 includes an article in which the surface is a first surface, the article further having a second surface facing away from the first surface, and the body is positioned between the first surface and the second surface such that the article is a sheet.

[0125] Embodiment 118 includes a method of making a material, comprising growing jeffvenite at a pressure less than 10 GPa.

[0126] Example 119 includes the method of Example 118, wherein the growing step is at a temperature of less than 1400K.

[0127] Example 120 includes the method of example 118, wherein jeffvenite is grown as a crystalline phase within the glass to form a glass-ceramic.

[0128] It should be understood that both the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments, and are incorporated into and constitute a part of this specification. The drawings illustrate various embodiments described herein and, together with the description, serve to explain the principles and operation of the claimed subject matter. [Brief description of the drawings]

[0129] [Figure 1] Top view of electronic device with glass ceramic article [Diagram 2] FIG. 1 is a perspective view of an electronic device including a glass-ceramic article. [Diagram 3] SEM micrograph of the crystal structure of a glass-ceramic containing a crystalline phase with the jeffvenite crystal structure. [Figure 4] SEM micrograph of the crystal structure of a glass-ceramic containing a crystalline phase with the jeffvenite crystal structure. [Diagram 5] High temperature X-ray diffraction 2θ plots showing the range of stability of various crystalline phases in glass-ceramics containing a crystalline phase with jeffvenite crystal structure and a tetragonal zirconia crystalline phase as a function of temperature [Figure 6A] SEM micrograph of the crystal structure of a glass-ceramic containing a crystalline phase with the jeffvenite crystal structure. [Figure 6B] SEM micrograph of the crystal structure of a glass-ceramic containing a crystalline phase with the jeffvenite crystal structure. [Figure 6C] SEM micrograph of the crystal structure of a glass-ceramic containing a crystalline phase with the jeffvenite crystal structure. [Figure 6D] SEM micrograph of the crystal structure of a glass-ceramic containing a crystalline phase with the jeffvenite crystal structure. [Figure 6E] SEM micrograph of the crystal structure of a glass-ceramic containing a crystalline phase with the jeffvenite crystal structure. [Figure 6F]SEM micrograph of the crystal structure of a glass-ceramic containing a crystalline phase with the jeffvenite crystal structure. [Figure 7] X-ray diffraction 2θ plots showing crystalline phases having jeffvenite crystal structure in exemplary glass-ceramic articles [Figure 8A] Schematic of a glass-ceramic article [Figure 8B] Cross-sectional view of a glass-ceramic article [Figure 9] Schematic of a glass-ceramic article [Figure 10] Graph showing total transmittance of a glass-ceramic article containing a crystalline phase having a jeffvenite crystal structure as a function of wavelength. [Figure 11] Graph showing diffuse transmittance of a glass-ceramic article containing a crystalline phase having a jeffvenite crystal structure as a function of wavelength. [Figure 12] Graph showing axial transmission of a glass-ceramic article containing a crystalline phase having a jeffvenite crystal structure as a function of wavelength. [Figure 13] Graph showing the scattering ratio of a glass-ceramic article containing a crystalline phase having a jeffvenite crystal structure as a function of wavelength. [Figure 14] FIG. 1 shows a window from the MDI Jade software used to characterize a glass-ceramic article. [Figure 15] FIG. 1 shows a window from the MDI Jade software used to characterize a glass-ceramic article. [Figure 16] FIG. 1 shows a window from the MDI Jade software used to characterize a glass-ceramic article. [Figure 17] FIG. 1 shows windows from Bruker Topas software used to characterize glass-ceramic articles. [Figure 18] FIG. 1 shows windows from Bruker Topas software used to characterize glass-ceramic articles. [Figure 19]FIG. 1 shows windows from Bruker Topas software used to characterize glass-ceramic articles. [Figure 20] FIG. 1 shows windows from Bruker Topas software used to characterize glass-ceramic articles. [Figure 21] FIG. 1 shows an XRD spectrum of a glass-ceramic article containing a crystalline phase having a jeffvenite crystal structure. [Figure 22] FIG. 1 shows an XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffvenite crystal structure. [Diagram 23] FIG. 1 shows an XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffvenite crystal structure. [Figure 24] FIG. 1 shows an XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffvenite crystal structure. [Diagram 25] FIG. 1 shows an XRD spectrum of a glass-ceramic article containing a crystalline phase having a jeffvenite crystal structure. [Figure 26] FIG. 1 shows an XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffvenite crystal structure. [Figure 27] FIG. 1 shows an XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffvenite crystal structure. [Figure 28] FIG. 1 shows an XRD spectrum of a glass-ceramic article containing a crystalline phase having a jeffvenite crystal structure. [Figure 29] FIG. 1 shows an XRD spectrum of a glass-ceramic article containing a crystalline phase having a jeffvenite crystal structure. [Diagram 30] Photograph of a transparent glass-ceramic article containing a crystalline phase having the jeffvenite crystal structure. [Diagram 31] Graph showing total transmittance of a glass-ceramic article containing a crystalline phase having a jeffvenite crystal structure as a function of wavelength. [Diagram 32] Graph showing diffuse transmittance of a glass-ceramic article containing a crystalline phase having a jeffvenite crystal structure as a function of wavelength. [Diagram 33] Graph showing the scattering ratio of a glass-ceramic article containing a crystalline phase having a jeffvenite crystal structure as a function of wavelength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0130] Reference will now be made in detail to various embodiments of precursor glasses and glass-ceramic articles produced therefrom. According to embodiments, the glass-ceramic article has a first side, a second side opposite the first side, and a periphery that defines the shape of the glass-ceramic article. The glass-ceramic article may further include a phase assemblage including one or more crystalline phases and a glass phase, the one or more crystalline phases including a crystalline phase having a jeffvenite crystal structure. Reference will now be made to various embodiments of the precursor glasses, glass-ceramic articles produced therefrom, and methods of producing the glass-ceramic articles with specific reference to the accompanying drawings.

[0131] Ranges may be expressed herein as from "about" one particular value, and / or to "about" another particular value. When such a range is expressed, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when values ​​are expressed as approximations, by use of the antecedent "about," it will be understood that the particular value forms another embodiment. It will be further understood that the endpoints of each of the ranges are significant both in relation to the other endpoint, and independently of the other endpoint.

[0132] As used herein, directional terms - e.g., up, down, right, left, front, back, upper and bottom - are used only with reference to the drawings as depicted and are not intended to imply absolute orientation.

[0133] Unless otherwise expressly stated, it is never intended that any method described herein be construed as requiring that its steps be performed in a particular order, or that any particular orientation of any apparatus be required. Thus, where a method claim does not actually recite an order in which its steps must be followed, or an apparatus claim does not actually recite an order or orientation for individual components, or where it is otherwise specifically stated in the claim or description that the steps are to be limited to a particular order, or where a particular order or orientation for the apparatus components is not recited, no order or orientation is ever intended to be implied. This applies to any possible non-expressive criteria of interpretation, including sequence of steps, flow of operations, order of components, or orientation of components; obvious meanings derived from grammatical construction or punctuation; and logical matters regarding the number or type of embodiments described in the specification.

[0134] As used herein, nouns include plural referents unless the context clearly indicates otherwise. Thus, for example, reference to an element includes aspects having two or more of such elements unless the context clearly indicates otherwise.

[0135] The term "substantially free," when used to describe the concentration and / or absence of a particular component in a precursor glass or glass-ceramic composition, means that the component has not been intentionally added to the precursor glass or glass-ceramic composition. However, the precursor glass or glass-ceramic composition may contain trace amounts of the component as contaminants or admixtures in amounts less than 0.05 mole percent.

[0136] In the embodiments of the precursor glass or glass-ceramic compositions described herein, concentrations of components (e.g., SiO, AlO, etc.) are specified in mole percent (mol %) on an oxide basis unless otherwise specified.

[0137] The transmittance data (total transmittance) are measured with a Lambda 950 UV / Vis Spectrophotometer manufactured by PerkinElmer Inc. (Waltham, Massachusetts, USA). The Lambda 950 instrument was fitted with a 150 mm integrating sphere. Data were collected using an open beam baseline and a Spectralon® reference reflectance disk. For total transmittance (Total Tx), the sample is fixed at the entry point of the integrating sphere. For diffuse transmittance (Diffuse Tx), the "Spectralon" reference reflectance disk above the exit port of the integrating sphere is removed to allow the on-axis light to exit the integrating sphere and enter the light trap. To determine the efficiency of the light trap, a zero offset measurement of the diffuse portion is made without a sample in place. To correct the diffuse transmittance measurements, the zero offset contribution is calculated using the formula: Diffuse Tx=Diffuse 測定値 -(zero offset * Measure the scattering ratio for all wavelengths as (%Diffuse Tx / %Total Tx).

[0138] The term "transparent" as used to describe articles herein refers to an article having an average transmittance of at least 75% for light in the wavelength range of 400 nm to 800 nm (endpoints included) at an article thickness of 0.6 mm.

[0139] The term "semi-transparent," when used to describe articles herein, unless otherwise specified in the claims, refers to an article having an average transmittance in the range of 20% to less than 75% for light in the wavelength range of 400 nm to 800 nm (inclusive) at an article thickness of 0.6 mm.

[0140] The term "opaque", when used to describe glass-ceramic articles formed from the glass-ceramic compositions herein, means that the glass-ceramic composition has an average transmittance of less than 20% when measured at normal incidence for light in the wavelength range of 400 nm to 800 nm (inclusive) at an article thickness of 0.6 mm.

[0141] As used herein, the term "CIELAB color space" refers to a color space defined by the International Commission on Illumination (CIE) in 1976. This color space represents color as three values: L, which represents lightness from black (0) to white (100); * , green (-) to red (+) a * , and blue (-) to yellow (+) b * Unless otherwise stated, L * , a * , and b * Values ​​are given for article thicknesses from 0.4 mm to 5 mm (end points included) across the thickness of the sample, under an F2 illuminant, with a standard observer angle of 10°. Unless otherwise stated, this means that each thickness within the thickness range is * , a * , and b * L within the specified range for coordinates * , a * , and b * For example, L in the range 55 to 96.5 * The colored glass article has a thickness within the range of 0.4 mm to 5 mm (e.g., 0.6 mm, 0.9 mm, 2 mm, etc.) and an L value within the range of 55 to 96.5. * It means that

[0142] The grain dimensions of the crystalline phase(s) of the glass-ceramics described herein are measured using scanning electron microscopy.

[0143] As used herein, the term "melting point" refers to the temperature at which the viscosity of the precursor glass or glass-ceramic composition reaches 200 poise (20 Pa * s) is referred to as the temperature at which

[0144] As used herein, the term "softening point" refers to the point at which the viscosity of a precursor glass or glass-ceramic composition is less than 1×10 7.6 Poise (1×10 6.6 Pa * The softening point is measured according to the parallel plate viscosimetry, which is a function of temperature of 10°C, as in ASTM C1351M. 7 From 10 9 Poise (10 6 From 10 8 Pa * s) Measure the viscosity of inorganic glass.

[0145] As used herein, the term "liquidus viscosity" refers to the viscosity of a glass-ceramic at the onset of devitrification (ie, at the liquidus temperature as determined according to the gradient furnace method per ASTM C829-81).

[0146] The elastic modulus of the glass-based articles (sometimes referred to as Young's modulus) is given in units of gigapascals (GPa). The elastic modulus of glass is determined by resonant ultrasonic spectroscopy on bulk samples of each glass-based article according to ASTM C623.

[0147] Vickers hardness can be measured using ASTM C1326 and C1327 (and its successors, all of which are incorporated herein by reference) "Standard Test Methods for Vickers Indentation Hardness of Advanced Ceramics," ASTM International, Conshohocken, Pennsylvania, USA. In some embodiments, the glass-ceramics exhibit such Vickers Indentation Crack Initiation Load values ​​after being chemically strengthened by ion exchange.

[0148] Fracture toughness can be measured using small square bars with chevron notches according to ASTM C1421-10, "Standard Test Methods for Determination of Fracture Toughness of Advanced Ceramics at Ambient Temperature," prior to ion-exchange strengthening of the glass-ceramic.

[0149] Compressive stress (including surface compressive stress) is measured by a surface stress meter (FSM), such as a commercially available instrument, such as the FSM-6000 manufactured by Orihara Seisakusho Co., Ltd. (Japan). Surface stress measurement relies on the measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass-ceramic. The SOC is then measured according to procedure C (glass disk method) described in ASTM standard C770-16, entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient," the contents of which are incorporated herein in their entirety. Depth of compression (DOC) is also measured with the FSM. Maximum central tension (CT) values ​​are measured using the Scattered Light Polariscope (SCALP) technique, which is known in the art.

[0150] The phrases "depth of compression" and "DOC" refer to the location in the glass-ceramic where compressive stress changes to tensile stress.

[0151] As used herein, the phrases "glass precursor" or "precursor glass" refer to a glass or glass article that contains (e.g., within a body of material, which may be uniformly distributed therein throughout the body) one or more nucleating agents and / or nucleation sites that, upon heat treatment, at least partially cause (e.g., promote) the nucleation of at least one crystalline phase in the glass.

[0152] As used herein, the phrase "glass-ceramic" refers to a material or article formed from a precursor glass material following nucleation of at least one crystalline phase in the precursor glass, such that the glass-ceramic comprises a residual glass phase and at least one crystalline phase (see generally FIG. 9 and associated disclosure).

[0153] As used herein, the phrase "predominant crystalline phase" refers to a crystalline phase that is present in a glass-ceramic in an amount (by weight % of the glass-ceramic) that is greater than the amount (by weight % of the glass-ceramic) of any other individual crystalline phase present in the glass-ceramic. For example, if a glass-ceramic contains crystalline phases A, B, and C, and crystalline phase A is the predominant crystalline phase, then the amount of crystalline phase A in the glass-ceramic is greater than the amount of crystalline phase B in the glass-ceramic, and greater than the amount of crystalline phase C in the glass-ceramic.

[0154] Articles formed from glass ceramics generally have improved fracture toughness compared to articles formed from glasses. This improvement may be due to the presence of grains in the glass ceramic, which may hinder crack growth. The fracture toughness of glass ceramics may be improved by decreasing the number of grains per unit volume of the glass ceramic, i.e., by increasing the grain size of the glass ceramic. However, the transparency or light transmission of the glass ceramic may decrease with increasing grain size. Specifically, the visible transmission of the glass ceramic may decrease significantly when the grain size is greater than 300 nm. Thus, a glass ceramic may have relatively good mechanical properties (such as fracture toughness) and relatively poor optical characteristics (such as light transmission or optical transmittance), or relatively poor mechanical properties and relatively good optical characteristics, but not both.

[0155] In addition, certain glass-ceramics may be strengthened by an ion-exchange process in which smaller alkali metal ions in the glass-ceramic are exchanged for larger alkali metal ions, for example, from a bath of molten alkali metal salt. As an example, a lithium-containing glass-ceramic may be strengthened with ion exchange by placing the glass-ceramic in a bath of molten alkali metal salts, such as salts of sodium and / or potassium, thereby promoting the exchange of lithium ions in the glass-ceramic with sodium and / or potassium ions in the bath. However, the recent demand for lithium for various applications has increased the cost and decreased availability of lithium raw materials, thereby increasing the overall cost of producing glass-ceramics containing lithium that can be strengthened with ion exchange. The glass-ceramics described herein do not require lithium to promote the desired ion-exchange performance.

[0156] Disclosed herein are precursor glasses and glass-ceramics formed therefrom that alleviate the problems discussed above.

[0157] Referring now to FIG. 9 , by way of example, a glass-ceramic article 810 is shown in accordance with one or more embodiments illustrated and described herein. As used herein, the phrase “glass-ceramic” refers to a material or article formed from a precursor glass material following nucleation of at least one crystalline phase in the precursor glass, such that the glass-ceramic includes a residual glass phase and at least one crystalline phase. Thus, the glass-ceramic article 810 includes both a glass phase 812 (e.g., an amorphous glass; a single-phase glass or a multiphase glass) and a polycrystalline ceramic phase (e.g., particles of a primary crystalline phase 814, optionally including particles of a secondary crystalline phase 816). The glass phase 812 may also be referred to as a “residual glass” or a “residual glass phase.” Possibly, the grains of crystalline phases 814, 816 may be non-uniformly distributed or directionally grown, such as by localized heat from a laser or by locating and / or orienting nucleation sites to guide the growth of the grains of crystalline phases 814, 816, and contemplated embodiments include such properties; however, generally, in the glass-ceramics disclosed herein, the grains of crystalline phases 814, 816 are uniformly or homogeneously distributed within the glass phase 812, such as throughout some, most, or all of the glass-ceramic article 810, and may be randomly oriented. Additionally, once nucleated from the precursor glass, the grains of crystalline phases 814, 816 may be grown to contact one another, overlap one another, interdigitate, and / or occupy much of the volume of the glass-ceramic article 810. Growing the grains of the crystalline phases 814, 816 to different sizes can affect the properties of the glass-ceramic article 810, which can be isotropic, uniformly positioned, or randomly oriented when the grains of the crystalline phases 814, 816 have grain sizes as disclosed herein and the article has sizes as disclosed herein. After nucleation and growth of the grains of the crystalline phases 814, 816, the glass phase 812 surrounds (e.g., contacts, encases, encapsulates) each or cluster of grains of the crystalline phases 814, 816.The glass-ceramic article 810 may have multiple crystalline phases, as indicated with respect to crystalline phases 814, 816, and / or multiple glassy phases 812.

[0158] The glass-ceramic embodiments described herein, such as the embodiment shown in FIG. 9, have a phase assemblage that includes one or more crystalline phases and a glass phase. At least one of the crystalline phases has a jeffvenite crystal structure. A crystalline phase having a jeffvenite crystal structure refers to a crystalline phase that has been identified as jeffvenite by X-ray diffraction (XRD) analysis. For example, XRD data (e.g., XRD spectrum) collected from a sample of glass-ceramic material, along with general compositional information about the composition of the sample (e.g., the batch composition from which the sample was prepared), can be input into MDI Jade Powder XRD Analysis software from Materials Data Inc. The software utilizes the input information, along with the International Center for Diffraction Data Powder Diffraction Files version 4 database (ICDD PDF-4 database), to identify crystalline phases in the sample based on the compositional information of the sample and the crystal structure of the phases determined from the XRD data. In an embodiment, the phase assemblage of the glass-ceramic may include at least one crystalline phase having a jeffvenite crystal structure as determined by this technique.

[0159] Based on the foregoing, unless otherwise specified or further defined herein, such as in the claims or elsewhere, the phrase "jafvenite crystal structure" refers to a crystalline phase or particles of a crystalline phase identified by XRD analysis as jefvenite, as described herein, and further characterizations provided herein will help clarify the various embodiments and shapes of crystalline phases having jefvenite crystal structure that may be included and claimed.

[0160] In embodiments, a crystalline phase having a jehvenite crystal structure is the predominant crystalline phase in the glass-ceramic. A crystalline phase having a jehvenite crystal structure may have attributes in common with jehvenite (e.g., composition, molecular structure, microstructure).

[0161] Jeffvenite, named after Jeffrey Harris and Ben Harte, is a mineral recently discovered as an inclusion in diamonds from the "super-deep" (i.e., greater than 300 km deep) in the Earth's mantle. Prior to its naming, Jeffvenite was called tetragonal-almandine-pyrope phase ("TAPP"). Jeffvenite is a tetragonal Mg3Al2Si3O 12 The term "tetragonal" refers to an otherwise cubic lattice that is stretched along one of the lattice vectors to form a rectangular basal prism having a square base ("a x a") and a height ("c" different from "a"), such as in space group I42d. A tetragonal crystal structure of jeffvenite may have a cell edge parameter α of about 6.5, such as 6.5231(1), within 0.1 of that, and a parameter c of about 18.2, such as 18.1756(3) Angstroms, within 0.1 of that. A crystalline phase having a jeffvenite crystal structure may have the tetragonal structure of jeffvenite, as described herein.

[0162] The density of Jeffvenite (itself) is 0.1 g / cm 3 Within 3.576g / cm 3 etc., about 3.6g / cm 3 The microhardness of the Jeffvenite (by itself) may be about 7, such as within 1 thereof. The Jeffvenite (by itself) may have a refractive index ω of about 1.7, such as 1.733(5), such as within 0.1 thereof, and an ε of about 1.7, such as 1.721, such as within 0.1 thereof, and may be uniaxial (-).

[0163] Mg3Al2Si3O 12is the ideal form of jeffvenite, jeffvenite can generally be described as a stoichiometric garnet composition similar to pyrope (Mg3Al2(SiO4)3))-almandine (Fe3Al2(SiO4)3) but with a tetragonal crystal structure and may contain other elements. In other words, structurally, jeffvenite and crystals with the jeffvenite crystal structure are (M1)(M2)2(M3)2(T1)(T2)2O 12 where M1 comprises magnesium (e.g., is mostly magnesium), M2 comprises aluminum (e.g., is mostly aluminum), M3 comprises magnesium (e.g., is mostly magnesium), and T1 and T2 comprise silicon (both are mostly silicon), and no two tetrahedra in such a crystal structure share any oxygen with each other. Jeffvenite is sometimes classified as an orthosilicate, i.e., a silicate containing the tetrahedral group SiO4 with a silicon to oxygen ratio of 1 to 4.

[0164] In the embodiments of the glass-ceramics described herein, the crystalline phase having the jeffvenite crystal structure is tetragonal Mg3Al2Si3O 12 It may at least comprise, consist essentially of (greater than 50% by mass), or consist essentially of.

[0165] In embodiments of the glass-ceramics described herein, a crystalline phase having a jeffvenite crystal structure (or a portion thereof) may be modified by the addition of zirconia (ZrO2). Without intending to be bound by any theory, it is believed that alumina (i.e., aluminum contribution) may be at least partially replaced in the jeffvenite crystal structure by magnesia (i.e., magnesium contribution) and zirconia (i.e., zirconium contribution). In such embodiments, the crystalline phase having a jeffvenite crystal structure (or a portion thereof) may be modified by the addition of zirconia (ZrO2). 3+x Zr x Al 2-2x SiO 12where x is from 0 to 1, inclusive. In embodiments, x may be from 0 to 0.6, inclusive. For example, and without limitation, a crystalline phase having a jeffvenite crystal structure (or a portion thereof) may have the composition: MgAlSiO 12 , Mg 3.1 Zr 0.1 Al 1.8 SiO 12 , Mg 3.2 Zr 0.2 Al 1.6 SiO 12 , Mg 3.3 Zr 0.3 Al 1.4 SiO 12 , Mg 3.4 Zr 0.4 Al 1.2 SiO 12 , Mg 3.5 Zr 0.5 AlSiO 12 , Mg 3.6 Zr 0.6 Al 0.8 SiO 12 , Mg 3.7 Zr 0.7 Al 0.6 SiO 12 , Mg 3.8 Zr 0.8 Al 0.4 SiO 12 , or Mg 3.9 Zr 0.9 Al 0.2 SiO 12 It may have.

[0166] In embodiments of the glass-ceramics described herein, the crystalline phase having the jeffvenite crystal structure (or a portion thereof) may be further modified by the addition of titania, tin oxide, iron oxide (FeO), manganese oxide, and / or zinc oxide. For example, titania (i.e., titanium contribution) and / or tin oxide (i.e., tin contribution) may be substituted for up to 50% of the zirconium in the jeffvenite crystal structure. Similarly, iron oxide (i.e., iron contribution), manganese oxide (i.e., manganese contribution), and / or zinc oxide (i.e., zinc contribution) may be substituted for a portion of the magnesium in the jeffvenite crystal structure. In such embodiments, the crystalline phase having the jeffvenite crystal structure (or a portion thereof) may have the following formula: (Mg,Fe,Mn,Zn) 3+x (Zr, Ti, Sn) x Al 2-2x SiO 12 where x is from 0 to 1 inclusive. In embodiments, x may be from 0 to 0.6 inclusive. For example, and without limitation, a crystalline phase having a jeffvenite crystal structure (or a portion thereof) may have a composition according to the formula: (Mg,Fe,Mn,Zn)AlSiO 12 , (Mg, Fe, Mn, Zn) 3.1 (Zr, Ti, Sn) 0.1 Al 1.8 SiO 12 , (Mg, Fe, Mn, Zn) 3.2 (Zr, Ti, Sn) 0.2 Al 1.6 SiO 12 , (Mg, Fe, Mn, Zn) 3.3 (Zr, Ti, Sn) 0.3 Al 1.4 SiO 12 , (Mg, Fe, Mn, Zn) 3.4 (Zr, Ti, Sn) 0.4 Al 1.2 SiO 12 , (Mg, Fe, Mn, Zn) 3.5 (Zr, Ti, Sn) 0.5 AlSiO 12 , (Mg, Fe, Mn, Zn) 3.6(Zr, Ti, Sn) 0.6 Al 0.8 SiO 12 , (Mg, Fe, Mn, Zn) 3.7 (Zr, Ti, Sn) 0.7 Al 0.6 SiO 12 , (Mg, Fe, Mn, Zn) 3.8 (Zr, Ti, Sn) 0.8 Al 0.4 SiO 12 , or (Mg, Fe, Mn, Zn) 3.9 (Zr, Ti, Sn) 0.9 Al 0.2 SiO 12 In these embodiments, it should be understood that the Fe, Mn, Zn, Ti, and Sn components in the formula are each optional and that the composition can be formed without one or more of these elements. For example, the composition can include no Fe but Mn, Ti, and Sn, or no Sn but Fe, Mn, Zn, and Ti. Thus, it should be understood that the formulas listed above can be written without one or more of Fe, Mn, Zn, Ti, and Sn.

[0167] It should be understood that other substitutions and modifications to the crystalline phase having the jeffvenite structure are contemplated and possible. For example, in the glass-ceramic embodiments described herein, the crystalline phase having the jeffvenite crystal structure (or a portion thereof) may be modified by the substitution of a divalent metal cation ("R 2+ The source of divalent metal cations (represented as ZnO or Fe) may be modified by the addition of metal oxides to the composition. Examples of divalent metal cations include, without limitation, Ca 2+ , Mn 2+ , Fe 2+ In these embodiments, the divalent metal cation may have an ionic radius of less than 1 Angstrom (0.1 nm). Similarly, a crystalline phase having a jeffvenite crystal structure (or a portion thereof) may contain tetravalent metal cations ("R4+ ") may be modified by the addition of metal oxides to the composition. Examples of tetravalent metal cations include, without limitation, Ti 4+ , Sn 4+ , Hf 4+ In such an embodiment, the crystalline phase having the jeffvenite crystal structure (or a portion thereof) is represented by the following formula: (Mg, R 2+ ) 3+x (Zr, R 4+ ) x Al 2-2x SiO 12 where x is from 0 to 1 inclusive. In embodiments, x may be from 0 to 0.6 inclusive. For example, and without limitation, a crystalline phase having a jeffvenite crystal structure (or a portion thereof) may have a composition according to the formula: 2+ )3Al2Si3O 12 , (Mg, R 2+ ) 3.1 (Zr, R 4+ ) 0.1 Al 1.8 SiO 12 , (Mg, R 2+ ) 3.2 (Zr, R 4+ ) 0.2 Al 1.6 SiO 12 , (Mg, R 2+ ) 3.3 (Zr, R 4+ ) 0.3 Al 1.4 SiO 12 , (Mg, R 2+ ) 3.4 (Zr, R 4+ ) 0.4 Al 1.2 SiO 12 , (Mg, R 2+ ) 3.5 (Zr, R 4+ ) 0.5 AlSiO 12 , (Mg, R 2+ ) 3.6 (Zr, R 4+ ) 0.6 Al 0.8 SiO 12 , (Mg, R2+ ) 3.7 (Zr, R 4+ ) 0.7 Al 0.6 SiO 12 , (Mg, R 2+ ) 3.8 (Zr, R 4+ ) 0.8 Al 0.4 SiO 12 , or (Mg, R 2+ ) 3.9 (Zr, R 4+ ) 0.9 Al 0.2 SiO 12 In these embodiments, R 2+ and R 4+ It should be understood that each of the components is optional and the composition can be formed without one or the other of these elements. Thus, the formula given above can be expressed as R 2+ and R 4+ It should be understood that one or the other may be described without the other.

[0168] In embodiments, one or more of the crystalline phases of the phase assemblage may include one or more minor crystalline phases. The one or more minor crystalline phases may be present in the glass-ceramic in amounts less than the major crystalline phase. In embodiments, the one or more minor crystalline phases may include tetragonal zirconia (ZrO2), ZrTiO4, or a combination thereof. However, it should be understood that other minor crystalline phases may also be present in the resulting glass-ceramic. In embodiments, one or more of the minor crystalline phases may enter the structure of a crystalline phase having a javenite crystalline structure (e.g., there may be a secondary phase within the lattice of the javenite crystalline phase).

[0169] In embodiments, the phase assemblage of the glass-ceramics described herein, as determined according to Rietveld refinement of an XRD spectrum, by weight (i.e., by weight %) of the glass-ceramic article, may include 25% or more by weight of one or more crystalline phases and 75% or less by weight of a glass phase, 30% or more by weight of one or more crystalline phases and 70% or less by weight of a glass phase, 40% or more by weight of one or more crystalline phases and 60% or less by weight of a glass phase, 50% or more by weight of one or more crystalline phases and 50% or less by weight of a glass phase, 60% or more by weight of one or more crystalline phases and 40% or less by weight of a glass phase, 70% or more by weight of one or more crystalline phases and 30% or less by weight of a glass phase, 80% or more by weight of one or more crystalline phases and 20% or less by weight of a glass phase. It should be understood that the crystalline phase content or glass content can fall within a subrange formed from any and all of the preceding endpoints. In embodiments, the crystalline phases and glass phases can be uniformly distributed throughout the glass-ceramic. At least some, most (greater than 50% by mass), or substantially all of such crystalline phases have a jeffvenite crystal structure (e.g., tetragonal stoichiometric garnet, MgAlSiO, as determined by XRD). 12 It should further be noted that the term "convolutional eigenvalue" may have the following general properties:

[0170] SiO2 may be the primary glass former in the precursor glass and glass-ceramic compositions described herein and may act to stabilize the network of the glass-ceramic. The concentration of SiO2 in the precursor glass and glass-ceramic composition should be high enough (e.g., 35% by weight or more) to form a crystalline phase when the precursor glass is heat treated to convert it to a glass-ceramic. The amount of SiO2 should be limited (e.g., 65 mol% or less) to control the melting point of the precursor glass or glass-ceramic composition, since the melting temperature of pure SiO2 or high SiO2 glasses is undesirably high. Thus, limiting the concentration of SiO2 may help improve the meltability and formability of the precursor glass or glass-ceramic composition.

[0171] In embodiments, the precursor glass or glass-ceramic composition may contain a positive amount of silica, e.g., an amount greater than the inclusion amount (0.05 mol % or more), e.g., from 35 mol % to 65 mol % SiO2. In an embodiment, the precursor glass or glass ceramic composition may be 35 mol% to 62 mol%, 35 mol% to 59 mol%, 35 mol% to 56 mol%, 35 mol% to 53 mol%, 35 mol% to 50 mol%, 35 mol% to 47 mol%, 35 mol% to 44 mol%, 35 mol% to 41 mol%, 35 mol% to 38 mol%, 38 mol% to 65 mol%, 41 mol% to 65 mol%, 42 mol% to 65 mol%, 43 mol% to 65 mol%, 44 mol% to 65 mol%, 45 mol% to 65 mol%, or 46 mol% to 65 mol%. , 47 mol% to 65 mol%, 48 mol% to 65 mol%, 49 mol% to 65 mol%, 50 mol% to 65 mol%, 51 mol% to 65 mol%, 52 mol% to 65 mol%, 53 mol% to 65 mol%, 54 mol% to 65 mol%, 55 mol% to 65 mol%, 56 mol% to 65 mol%, 57 mol% to 65 mol%, 58 mol% to 65 mol%, 59 mol% to 65 mol%, 60 mol% to 65 mol%, 61 mol% to 65 mol%, or any and all subranges formed from any of these endpoints. In some embodiments, the precursor glass or glass-ceramic composition may include 48 mol% to 54 mol% SiO2. In embodiments, the concentration of SiO2 may be 40 mol% or more, 45 mol% or more, or 50 mol% or more. In embodiments, the concentration of SiO2 may be 65 mol% or less, 60 mol% or less, or 55 mol% or less.

[0172] Al2O3, like SiO2, may also stabilize the glass network and, in addition, provide improved mechanical properties and chemical durability to the glass-ceramic. The amount of Al2O3 may also be adjusted to control the viscosity of the precursor glass or glass-ceramic composition. However, too much Al2O3 will increase the viscosity of the glass melt. In embodiments, the precursor glass or glass-ceramic composition may include from 5 mol % to 20 mol % Al2O3. In an embodiment, the concentration of Al2O3 in the precursor glass or glass ceramic composition is a positive amount, e.g., an amount greater than the amount of incorporation (0.05 mol% or more), e.g., from 5 mol% to 20 mol%, from 5 mol% to 19 mol%, from 5 mol% to 18 mol%, from 5 mol% to 17 mol%, from 5 mol% to 16 mol%, from 5 mol% to 15 mol%, from 5 mol% to 14 mol%, from 5 mol% to 13 mol%, from 5 mol% to 12 mol%, from 5 mol% to 11 mol%, from 5 mol% to 10 mol%, from 5 mol% to 9 mol%, from 5 mol% to 8 mol%, from 5 mol% to 7 mol%, In some embodiments, the concentration of Al2O3 in the precursor glass or glass-ceramic composition may be 9 mol% to 13 mol%, or less, 5 mol% to 6 mol%, 6 mol% to 20 mol%, 7 mol% to 20 mol%, 8 mol% to 20 mol%, 9 mol% to 20 mol%, 10 mol% to 20 mol%, 11 mol% to 20 mol%, 12 mol% to 20 mol%, 13 mol% to 20 mol%, 14 mol% to 20 mol%, 15 mol% to 20 mol%, 16 mol% to 20 mol%, 17 mol% to 20 mol%, 18 mol% to 20 mol%, 19 mol% to 20 mol%, or any and all subranges formed from any of these endpoints. In embodiments, the concentration of Al2O3 in the precursor glass or glass-ceramic composition may be 9 mol% to 13 mol%. In embodiments, the concentration of Al2O3 in the precursor glass or glass-ceramic composition may be 5 mol% or more, 7 mol% or more, or 10 mol% or more.In embodiments, the concentration of Al2O3 in the precursor glass or glass-ceramic composition may be 20 mol% or less, 15 mol% or less, 12 mol% or less, or 10 mol% or less.

[0173] In embodiments, the precursor glass or glass ceramic composition may contain a positive amount of MgO, e.g., an amount greater than the incorporation amount (0.05 mol % or more), e.g., 10 mol % or more to 45 mol % or less of MgO. In embodiments, the precursor glass or glass ceramic composition may contain 7 mol % or more to 65 mol % or less of MgO. The addition of MgO may increase the elastic modulus of the precursor glass and the resulting glass ceramic. MgO may also replace Al2O3 in the glass network, creating a more open network and improving ion mobility in the glass network. Without intending to be bound by theory, the addition of MgO may increase the crystallinity of the glass-ceramic composition. In an embodiment, the concentration of MgO in the precursor glass or glass-ceramic composition is from 7 mol% to 65 mol%, from 7 mol% to 60 mol%, from 7 mol% to 55 mol%, from 7 mol% to 50 mol%, from 7 mol% to 48 mol%, from 7 mol% to 46 mol%, from 7 mol% to 44 mol%, from 7 mol% to 42 mol%, from 7 mol% to 40 mol%, from 7 mol% to 38 mol%, from 7 mol% to 36 mol%, from 7 mol% to 34 mol%, from 7 mol% to 32 mol%, from 7 mol% to 30 mol%, from 7 mol% to 28 mol%, from 7 mol% to 26 mol%, from 7 mol% to 24 mol%, from 7 mol% to 22 mol%, from 7 mol% to 20 mol%, % or less, 7 mol% or more to 18 mol% or less, 7 mol% or more to 16 mol% or more, 7 mol% or more to 14 mol% or less, 7 mol% or more to 12 mol% or less, 7 mol% or more to 10 mol% or less, 9 mol% or more to 50 mol% or less, 10 mol% or more to 65 mol% or more, 10 mol% or more to 60 mol% or less, 10 mol% or more to 55 mol% or less, 10 mol% or more to 45 mol% or less, 10 mol% or more to 42 mol% or less, 10 mol% or more to 40 mol% or less, 10 mol% or more to 38 mol% or less, 10 mol% or more to 36 mol% or less, 10 mol% or more to 34 mol% or less, 10 mol% or more to 32 mol% or less, 10 mol% or more to 30 mol% or less, 10 mol% or more to 28 mol% or less, 10 mol% or more to 26 mol% or less, 10 mol% or more to 24 mol% or less,10 mol% or more to 22 mol% or less, 10 mol% or more to 20 mol% or less, 10 mol% or more to 18 mol% or less, 10 mol% or more to 16 mol% or less, 10 mol% or more to 14 mol% or less, 10 mol% or more to 12 mol% or less, 11 mol% or more to 50 mol% or less, 12 mol% or more to 60 mol% or less, 12 mol% or more to 45 mol% or less, 13 mol% or more to 65 mol% or less, 13 mol% or more to 50 mol% or less, 14 mol% or more to 60 mol% or less, 14 mol% or more to 45 mol% or less, 15 mol% or more to 65 mol% or less, 15 mol% or more to to 50 mol% or less, 16 mol% or more to 65 mol% or less, 16 mol% or more to 45 mol% or less, 17 mol% or more to 65 mol% or less, 17 mol% or more to 50 mol% or less, 18 mol% or more to 60 mol% or less, 18 mol% or more to 45 mol% or less, 19 mol% or more to 65 mol% or less, 19 mol% or more to 50 mol% or less, 20 mol% or more to 65 mol% or less, 20 mol% or more to 45 mol% or less, 21 mol% or more to 65 mol% or less, 21 mol% or more to 50 mol% or less, 22 mol% or more to 65 mol% or less, 22 mol% or more to 45 mol% or less, 23 mol% or more to 65 mol% or less, 23 mol% or more to 50 mol% or less, 24 mol% or more to 60 mol% or less, 24 mol% or more to 45 mol% or less, 25 mol% or more to 65 mol% or less, 25 mol% or more to 50 mol% or less, 26 mol% or more to 60 mol% or less, 26 mol% or more to 45 mol% or less, 27 mol% or more to 65 mol% or less, 27 mol% or more to 50 mol% or less, 28 mol% or more to 60 mol% or less, 28 mol% or more to 45 mol% or less, 29 mol% or more to 65 mol% or less, 29 mol% or more to 50 mol% or less, 30 mol% or more to 60 mol% or less, 30 mol% to 45 mol% or less, 31 mol% to 65 mol% or less, 31 mol% to 50 mol% or less, 32 mol% to 60 mol% or less, 32 mol% to 45 mol% or less, 33 mol% to 65 mol% or less, 33 mol% to 50 mol% or less, 34 mol% to 60 mol% or less, 34 mol% to 45 mol% or less, 35 mol% to 65 mol% or less, 35 mol% to 65 mol% or less, 35 mol% to 50 mol% or less, 36 mol% to 60 mol% or less, 36 mol% to 45 mol% or less,37 mol % to 65 mol %, 37 mol % to 50 mol %, 38 mol % to 60 mol %, 38 mol % to 45 mol %, 39 mol % to 65 mol %, 39 mol % to 50 mol %, 40 mol % to 60 mol %, 40 mol % to 45 mol %, 41 mol % to 65 mol %, 41 mol % to 50 mol %, 42 mol % to 60 mol %, 42 mol % to 45 mol %, 43 mol % to 65 mol %, 43 mol % to 50 mol %, 45 mol % to 50 mol %, 47 mol % to 50 mol %, or any and all subranges formed from any of these endpoints. In embodiments, the concentration of MgO in the precursor glass or glass ceramic composition may be 7 mol% or more, 10 mol% or more, 20 mol% or more, 25 mol% or more, or 30 mol% or more. In embodiments, the concentration of MgO may be 65 mol% or less, 60 mol% or less, 55 mol% or less, 50 mol% or less, 45 mol% or less, 40 mol% or less, 35 mol% or less, or 30 mol% or less. Without intending to be bound by theory, as the concentration of MgO in the glass ceramic composition increases, the opacity of the glass ceramic may increase. Similarly, as the concentration of MgO in the glass ceramic composition decreases, the transparency may improve. However, if the concentration of MgO in the glass ceramic composition is too low, the glass ceramic composition may become hazy in appearance.

[0174] In embodiments, the precursor glass or glass-ceramic composition may include Na2O. The addition of Na2O may reduce the liquidus viscosity of the glass, which in turn may aid in forming or shaping the precursor glass. Na2O may also promote ion-exchange strengthening of the resulting glass-ceramic, since most of the Na2O present in the precursor glass partitions into the residual glass phase after heat treatment (e.g., ceramization). In an embodiment, the concentration of NaO in the precursor glass or glass ceramic composition may be from 0 mol% or more, e.g., a positive amount, e.g., an amount greater than the amount of inclusion (0.05 mol% or more), to 15 mol%, from 0 mol% to 13 mol%, from 0 mol% to 11 mol%, from 0 mol% to 9 mol%, from 0 mol% to 7 mol%, from 0 mol% to 5 mol%, from 0 mol% to 3 mol%, from 0 mol% to 1 mol%, from 1 mol% to 15 mol%, from 1 mol% to 13 mol%, from 1 mol% to 11 mol%, from 1 mol% to 9 mol%, from 1 mol% to 7 mol%, from 1 mol% to 5 mol%, from 1 mol% to 3 mol%, from 2 mol% to 15 mol%, from 2 mol% or more, from above 13 mol% or less, from 2 mol% to 11 mol% or less, from 2 mol% to 9 mol% or less, from 2 mol% to 7 mol% or less, from 2 mol% to 5 mol% or less, from 2 mol% to 3 mol% or less, from 3 mol% to 15 mol% or less, from 4 mol% to 15 mol% or less, from 5 mol% to 15 mol% or less, from 6 mol% to 15 mol% or less, from 7 mol% to 15 mol% or less, from 8 mol% to 15 mol% or less, from 9 mol% to 15 mol% or less, from 10 mol% to 15 mol% or less, from 11 mol% to 15 mol% or less, from 12 mol% to 15 mol% or less, from 13 mol% to 15 mol% or less, from 14 mol% to 15 mol% or less, or any and all subranges formed from any of these endpoints. In embodiments, the concentration of Na2O in the precursor glass or glass-ceramic composition may be 0 mol% or more, 5 mol% or more, or 10 mol% or more. In embodiments, the concentration of Na2O may be 15 mol% or less, 10 mol% or less, or 5 mol% or less.In embodiments, the precursor glass or glass-ceramic composition may be substantially free of Na2O.

[0175] In embodiments, the precursor glass or glass-ceramic composition may include KO. The addition of KO may reduce the liquidus viscosity of the glass, which in turn may aid in forming or shaping the precursor glass. KO may also promote ion-exchange strengthening of the resulting glass-ceramic, since most of the KO partitions into the glass phase after ceramming. In an embodiment, the concentration of K2O in the precursor glass or glass ceramic composition may be from 0 mol% or more, e.g., a positive amount, e.g., an amount greater than the amount of inclusion (0.05 mol% or more), to 15 mol%, from 0 mol% or more to 13 mol%, from 0 mol% or more to 11 mol%, from 0 mol% or more to 9 mol%, from 0 mol% or more to 7 mol%, from 0 mol% or more to 5 mol%, from 0 mol% or more to 3 mol%, from 0 mol% or more to 1 mol%, from 1 mol% or more to 15 mol%, from 1 mol% or more to 13 mol%, from 1 mol% or more to 11 mol%, from 1 mol% or more to 9 mol%, from 1 mol% or more to 7 mol%, from 1 mol% or more to 5 mol%, from 1 mol% or more to 3 mol%, from 2 mol% or more to 15 ... from above 13 mol% or less, from 2 mol% to 11 mol% or less, from 2 mol% to 9 mol% or less, from 2 mol% to 7 mol% or less, from 2 mol% to 5 mol% or less, from 2 mol% to 3 mol% or less, from 3 mol% to 15 mol% or less, from 4 mol% to 15 mol% or less, from 5 mol% to 15 mol% or less, from 5 mol% to 15 mol% or less, from 6 mol% to 15 mol% or less, from 7 mol% to 15 mol% or less, from 8 mol% to 15 mol% or less, from 9 mol% to 15 mol% or less, from 10 mol% to 15 mol% or less, from 11 mol% to 15 mol% or less, from 12 mol% to 15 mol% or less, from 13 mol% to 15 mol% or less, or any and all subranges formed from any of these endpoints. In embodiments, the concentration of K2O in the precursor glass or glass-ceramic composition can be 0 mol% or more, 5 mol% or more, or 10 mol% or more. In embodiments, the concentration of K2O can be 15 mol% or less, 10 mol% or less, or 5 mol% or less.In embodiments, the precursor glass or glass-ceramic composition may be substantially free of K2O.

[0176] In embodiments, Na2O(mol%)+K2O(mol%) in the precursor glass or glass-ceramic compositions described herein may be greater than or equal to 0 mol% and less than or equal to 15 mol%.In embodiments, NaO (mol%) + KO (mol%) in the precursor glass or glass-ceramic composition described herein is in the range of 0 mol% to 15 mol%, 0 mol% to 13 mol%, 0 mol% to 11 mol%, 0 mol% to 9 mol%, 0 mol% to 7 mol%, 0 mol% to 5 mol%, 1 mol% to 15 mol%, 1 mol% to 13 mol%, 1 mol% to 11 mol%, 1 mol% to 9 mol%, 1 mol% to 7 mol%, 1 mol% to 5 mol%, 2 mol% to 15 mol%, 2 mol% to 13 mol%, 1 mol% to 11 mol%, 1 mol% to 9 mol%, 1 mol% to 7 mol%, 1 mol% to 5 mol%, 2 mol% to 15 mol%, 2 mol% to 15 mol%, 2 mol% to 13 mol%, 1 mol% to 11 mol%, 2 mol% to 9 mol%, 2 mol% to 7 mol%, 2 mol% to 5 mol%, 2 mol% to 1 ...5 mol%, 2 mol% to 13 mol%, 1 mol% to 11 mol%, 2 mol% to 9 mol%, 2 mol% to 7 mol%, 2 mol % to 15 mol%, 2 mol% to 13 mol%, 2 mol% to 11 mol%, 2 mol% to 9 mol%, 2 mol% to 7 mol%, 2 mol% to 5 mol%, 3 mol% to 15 mol%, 3 mol% to 13 mol%, 3 mol% to 11 mol%, 3 mol% to 9 mol%, 3 mol% to 7 mol%, 3 mol% to 5 mol%, 4 mol% to 15 mol%, 4 mol% to 13 mol%, 4 mol% to 11 mol%, 4 mol% to 9 mol%, 4 mol% or more to 7 mol%, 4 mol% or more to 5 mol%, 5 mol% or more to 15 mol%, 5 mol% or more to 13 mol%, 5 mol% or more to 11 mol%, 5 mol% or more to 9 mol%, 5 mol% or more to 7 mol%, 6 mol% or more to 15 mol%, 6 mol% or more to 13 mol%, 6 mol% or more to 11 mol%, 6 mol% or more to 9 mol%, 6 mol% or more to 7 mol%, 7 mol% or more to 15, mol%, 7 mol% or more to 13 mol%, 7 mol% or more to 11 mol%, 7 mol% or more to 9 mol%, 8 mol% from 8 mol% to 13 mol% or less, from 8 mol% to 11 mol% or less, from 8 mol% to 9 mol% or less, from 9 mol% to 15 mol% or less, from 9 mol% to 13 mol% or less, from 9 mol% to 11 mol% or less, from 10 mol% to 15 mol% or less, from 10 mol% to 13 mol% or less, from 10 mol% to 11 mol% or less, from 11 mol% to 15 mol% or less, from 11 mol% to 13 mol% or less, from 13 mol% to 15 mol% or less, or any and all subranges formed from any of these endpoints.In embodiments, the concentration of Na2O(mol%)+K2O(mol%) in the precursor glass or glass-ceramic composition may be 2 mol% or more, 3 mol% or more, 5 mol% or more, or 10 mol% or more. In embodiments, the concentration of Na2O(mol%)+K2O(mol%) may be 15 mol% or less, 10 mol% or less, or 5 mol% or less. In embodiments, Na2O(mol%) / (Na2O(mol%)+K2O(mol%)) may be 0.2 or more, or even 0.3 or more, to improve the ion-exchangeability of the resulting glass-ceramic.

[0177] In embodiments, the ratio of Na2O (mol %) to K2O (mol %) can be about 1:3, about 2:5, or about 1:1, e.g., as shown in the Examples, an amount of Na2O in mol % that is at least 33% or more of the amount of K2O in certain compositions disclosed herein (i.e., an amount of K2O that is at least 33% or more of the amount of Na2O), e.g., an amount of Na2O in mol % that is at least 40% or more of the amount of K2O, or vice versa, e.g., an amount of Na2O in mol % that is at least 50% or more of the amount of K2O, or vice versa, e.g., an amount of Na2O in mol % that is at least 60% or more of the amount of K2O, or vice versa, e.g., an amount of Na2O in mol % that is at least 70% or more of the amount of K2O, or vice versa, e.g., an amount of Na2O in mol % that is at least 80% or more of the amount of K2O, or vice versa, e.g., an amount of Na2O in mol % that is at least 90% or more of the amount of K2O, or vice versa. Without intending to be bound by theory, it is believed that the ratio of Na2O (mol %) to K2O (mol %) may be adjusted to improve the transparency of the glass-ceramic composition.

[0178] In embodiments, the precursor glass or glass-ceramic composition may include ZrO2. Without intending to be bound by theory, it is believed that ZrO2 acts as a nucleating agent that promotes the nucleation of a crystalline phase having a jeffvenite crystal structure during heat treatment at ambient atmospheric pressure (i.e., about 100 kPa). In embodiments, the ZrO2 may be tetragonal ZrO2. In an embodiment, the concentration of ZrO2 in the precursor glass or glass ceramic composition may be from 0 mol% or more, e.g., a positive amount, e.g., an amount greater than the amount of inclusion (0.05 mol% or more), to 7 mol%, from 0 mol% or more to 7 mol%, from 0 mol% or more to 6 mol%, from 0 mol% or more to 5 mol%, from 0 mol% or more to 4 mol%, from 0 mol% or more to 3 mol%, from 0 mol% or more to 2 mol%, from 0 mol% or more to 1 mol%, from 1 mol% or more to 7 mol%, from 1 mol% or more to 6 mol%, from 1 mol% or more to 5 mol%, from 1 mol% or more to 4 mol%, from 1 mol% or more to 3 mol%, from 1 mol% or more to 2 mol%, from 1.5 mol% or more to 7 mol%, from 1.5 mol% or more to 6 mol%, from 1.5 mol% or more to 6 mol%, from 1.5 mol% or more to 2 ... to 5 mol% or less, greater than 1.5 mol% to 4 mol% or less, greater than 1.5 mol% to 3 mol% or less, greater than 1.5 mol% to 2 mol% or less, 2 mol% or more to 7 mol% or less, 2 mol% or more to 6 mol% or less, 2 mol% or more to 5 mol% or less, 2 mol% or more to 4 mol% or less, 2 mol% or more to 3 mol% or more to 7 mol% or less, 3 mol% or more to 6 mol% or less, 3 mol% or more to 5 mol% or less, 3 mol% or more to 4 mol% or less, 4 mol% or more to 7 mol% or less, 4 mol% or more to 6 mol% or less, 4 mol% or more to 5 mol% or less, 5 mol% or more to 7 mol% or less, 5 mol% or more to 6 mol% or less, 6 mol% or more to 7 mol% or less, or any and all subranges formed from any of these endpoints. In embodiments, the concentration of ZrO2 in the precursor glass or glass-ceramic composition may be greater than 1.5 mol%, 2 mol% or more, 3 mol% or more, or 4 mol% or more. In embodiments, the concentration of ZrO2 may be 7 mol% or less, 6 mol% or less, or 5 mol% or less. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of ZrO2.

[0179] In embodiments, the precursor glass or glass-ceramic composition may include HfO2. Without intending to be bound by theory, it is believed that HfO2 functions as a nucleating agent to promote the formation of crystalline phases during heat treatment. In embodiments, HfO2 may be used as a nucleating agent in addition to or instead of ZrO2. HfO2 may also help to lower the liquidus of the precursor glass. In embodiments, the concentration of HfO2 in the precursor glass or glass-ceramic composition may be from 0 mol% or more, e.g., a positive amount, e.g., an amount greater than the inclusion amount (0.05 mol% or more), to 12 mol% or less.In an embodiment, the concentration of HfO2 in the precursor glass or glass ceramic composition is 0 mol% to 12 mol%, 0 mol% to 10 mol%, 0 mol% to 7 mol%, 0 mol% to 6 mol%, 0 mol% to 5 mol%, 0 mol% to 4 mol%, 0 mol% to 3 mol%, 0 mol% to 2 mol%, 0 mol% to 1 mol%, 1 mol% to 12 mol%, 1 mol% to 10 mol%, 1 mol% to 7 mol%, 1 mol% to 6 mol%, 1 mol% to 5 mol%, 1 mol% to 4 mol%, 1 mol% to 3 mol%, 1 mol% to 2 mol%, 2 mol% to 12 mol%, 2 mol% to 10 mol%, 2 mol% to 7 mol%, 2 mol% to 6 ... and 5 mol%, 2 mol% to 4 mol%, 2 mol% to 3 mol%, 3 mol% to 12 mol%, 3 mol% to 10 mol%, 3 mol% to 7 mol%, 3 mol% to 6 mol%, 3 mol% to 5 mol%, 3 mol% to 4 mol%, 4 mol% to 12 mol%, 4 mol% to 10 mol%, 4 mol% to 7 mol%, 4 mol% to 6 mol%, 4 mol% to 5 mol%, 5 mol% to 12 mol%, 5 mol% to 10 mol%, 5 mol% to 7 mol%, 5 mol% to 6 mol%, 4 mol% to 5 mol%, 5 mol% to 12 mol%, 5 mol% to 10 mol%, 5 mol% to 7 mol%, 5 mol% to 6 mol%, 6 mol% to 12 mol%, 6 mol% to 10 mol%, 6 mol% to 7 mol%, or any and all subranges formed from any of these endpoints. In embodiments, the concentration of HfO2 in the precursor glass or glass-ceramic composition may be 1 mol% or more, 2 mol% or more, or 3 mol% or more. In embodiments, the concentration of HfO2 may be 12 mol% or less, 10 mol% or less, 7 mol% or less, 6 mol% or less, or 5 mol% or less. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of HfO2.

[0180] In embodiments, the precursor glass or glass ceramic composition may include TiO2. Without intending to be bound by theory, it is believed that TiO2 acts as a nucleating agent to promote the formation of crystalline phases during heat treatment. Increasing the concentration of TiO2 may also impart color to the precursor glass and the resulting glass-ceramic. In embodiments, the concentration of TiO2 in the precursor glass or glass-ceramic composition may be from 0 mol% or more, e.g., a positive amount, e.g., an amount greater than the inclusion amount (0.05 mol% or more) to 7 mol% or less, 0 mol% or more to 6 mol% or less, 0 mol% or more to 5 mol% or less, 0 mol% or more to 4 mol% or less, 0 mol% or more to 3 mol% or less, 0 mol% or more to 2 mol% or less, 0 mol% or more to 1 mol% or less, 0.3 mol% or more to 7 mol% or more, and the like. 0.3 mol% or more to 6 mol% or less, 0.3 mol% or more to 5 mol% or less, 0.3 mol% or more to 4 mol% or less, 0.3 mol% or more to 3 mol% or less, 0.3 mol% or more to 2 mol% or less, 0.3 mol% or more to 1 mol% or less, 0.5 mol% or more to 7 mol% or less, 0.5 mol% or more to 6 mol% or less, 0.5 mol% or more to 5 mol% or less, 0.5 mol% or more to 4 mol% or less, 0.5 mol% or more to 3 ... mol% or more to 2 mol% or less, 0.5 mol% or more to 1 mol% or less, 1 mol% or more to 7 mol% or less, 1 mol% or more to 6 mol% or less, 1 mol% or more to 5 mol% or less, 1 mol% or more to 4 mol% or less, 1 mol% or more to 3 mol% or less, 1 mol% or more to 2 mol% or less, 2 mol% or more to 7 mol% or less, 2 mol% or more to 6 mol% or less, 2 mol% or more to 5 mol% or less, 2 mol% or more to 4 mol% or less, 2 mol% or more to 3 mol% or less The concentration of TiO2 in the precursor glass or glass-ceramic composition may be 0 mol% or more, 1 mol% or more, or 2 mol% or more, 3 mol% or more to 7 mol% or less, 3 mol% or more to 6 mol% or less, 3 mol% or more to 5 mol% or less, 3 mol% or more to 4 mol% or less, 4 mol% or more to 7 mol% or less, 4 mol% or more to 6 mol% or less, 4 mol% or more to 5 mol% or less, 5 mol% or more to 7 mol% or less, 5 mol% or more to 6 mol% or less, 6 mol% or more to 7 mol% or less, or any and all subranges formed from any of these endpoints. In embodiments, the concentration of TiO2 in the precursor glass or glass-ceramic composition may be 0 mol% or more, 1 mol% or more, or 2 mol% or more.In embodiments, the concentration of TiO2 may be 7 mol% or less, 6 mol% or less, or 5 mol% or less. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of TiO2.

[0181] In embodiments, ZrO2(mol%)+TiO2(mol%) in the precursor glass or glass ceramic compositions described herein can be 2.0 mol% or more, 3.0 mol% or more, or even 4.0 mol% or more. In embodiments, ZrO2(mol%) / (ZrO2(mol%)+TiO2(mol%)) in the precursor glass or glass ceramic compositions described herein can be 0.3 or more. Without intending to be bound by theory, if ZrO2(mol%) / (ZrO2(mol%)+TiO2(mol%)) in the precursor glass or glass ceramic composition is less than 0.3, then the predominant crystalline phase in the glass ceramic can be a forsterite crystalline phase instead of a crystalline phase having a jeffvenite crystalline structure, which would be undesirable.

[0182] In embodiments, the precursor glass or glass-ceramic composition may include SnO2. SnO2 primarily acts as a fining agent in the precursor glass composition. However, the addition of SnO2 may also assist nucleating agents (such as TiO2 and ZrO2) in nucleating crystalline phases during heat treatment. In embodiments, the concentration of SnO2 in the precursor glass or glass-ceramic composition can be from 0 mol% to 0.2 mol%, from 0 mol% to a positive amount, e.g., an amount greater than the inclusion amount (e.g., 0.05 mol% or more) to 0.18 mol%, from 0 mol% to 0.16 mol%, from 0 mol% to 0.14 mol%, from 0 mol% to 0.12 mol%, from 0 mol% to 0.11 mol%, from 0 mol% to 0.1 mol%, from 0 mol% to 0.08 mol% to 0.2 mol%, from 0.09 mol% to 0.2 mol%, from 0.1 mol% to 0.2 mol%, from 0.1 mol% to 0.2 mol%, from 0.12 mol% to 0.2 mol%, from 0.13 mol% to 0.2 mol%, from 0.14 mol% to 0.2 mol%, or any and all subranges formed from any of these endpoints. In embodiments, the concentration of SnO2 in the precursor glass or glass-ceramic composition may be 0 mol% or more, 0.08 mol% or more, or 0.09 mol% or more. In embodiments, the concentration of SnO2 may be 0.2 mol% or less, 0.18 mol% or less, or 0.16 mol% or less. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of SnO2.

[0183] In embodiments, the precursor glass or glass-ceramic composition may include BaO, which can increase the refractive index of the residual glass in the glass-ceramic to better match the refractive index of a crystalline phase having a jeffvenite crystal structure in the glass-ceramic. In an embodiment, the concentration of BaO in the precursor glass or glass ceramic composition may be from 0 mol % or more, e.g., a positive amount, e.g., an amount greater than the amount of inclusion (0.05 mol % or more), to 8 mol %, from 0 mol % to 7 mol %, from 0 mol % to 6 mol %, from 0 mol % to 5 mol %, from 0 mol % to 4 mol %, from 0 mol % to 3 mol %, from 0 mol % to 2 mol %, from 0 mol % to 1 mol %, from 1 mol % to 8 mol %, from 1 mol % to 7 mol %, from 1 mol % to 6 mol %, from 1 mol % to 5 mol %, from 1 mol % to 4 mol %, from 1 mol % to 3 mol %, from 1 mol % to 2 mol %, from 2 mol % to 8 mol %, from 2 mol % to 7 mol % , 2 mol% to 6 mol%, 2 mol% to 5 mol%, 2 mol% to 4 mol%, 2 mol% to 3 mol%, 3 mol% to 8 mol%, 3 mol% to 7 mol%, 3 mol% to 6 mol%, 3 mol% to 5 mol%, 3 mol% to 4 mol%, 4 mol% to 8 mol%, 4 mol% to 7 mol%, 4 mol% to 6 mol%, 4 mol% to 5 mol%, 5 mol% to 8 mol%, 5 mol% to 7 mol%, 5 mol% to 6 mol%, 6 mol% to 8 mol%, 6 mol% to 7 mol%, 7 mol% to 8 mol%, or any and all subranges formed from any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of BaO.

[0184] In an embodiment, the precursor glass or glass ceramic composition may include ZnO. The addition of ZnO increases the refractive index of the residual glass in the glass ceramic to better match the refractive index of the crystalline phase having the jeffvenite crystal structure in the glass ceramic. Without intending to be bound by theory, it is believed that the addition of ZnO may replace at least a portion of the Mg in the jeffvenite crystal structure with Zn. ZnO may also help stabilize the precursor glass, prevent devitrification, and reduce liquidus viscosity. However, too much ZnO may prevent the formation of the crystalline phase having the jeffvenite crystal structure during ceramization. In an embodiment, the concentration of ZnO in the precursor glass or glass ceramic composition may be from 0 mol% or more, e.g., a positive amount, e.g., an amount greater than the amount of incorporation (0.05 mol% or more), to 15 mol%, from 0 mol% to 14 mol%, from 0 mol% to 13 mol%, from 0 mol% to 12 mol%, from 0 mol% to 11 mol%, from 0 mol% to 10 mol%, from 0 mol% to 9 mol%, from 0 mol% to 8 mol%, from 0 mol% to 7 mol%, from 0 mol% to 6 mol%, from 0 mol% to 5 mol%, from 0 mol% to 4 mol%, from 0 mol% to 3 mol%, from 0 mol% to 2 mol%, from 0 mol% to 1 mol%, from 1 mol% to 15 mol%, from 1 mol% to 14 mol%, from 1 mol% to 13 mol%, mol% or less, 1 mol% or more to 12 mol% or less, 1 mol% or more to 11 mol% or more, 1 mol% or more to 10 mol% or less, 1 mol% or more to 9 mol% or less, 1 mol% or more to 8 mol% or less, 1 mol% or more to 7 mol% or less, 1 mol% or more to 6 mol% or less, 1 mol% or more to 5 mol% or less, 1 mol% or more to 4 mol% or less, 1 mol% or more to 3 mol% or less, 1 mol% or more to 2 mol% or less, 2 mol% or more to 15 mol% or less, 2 mol% or more to 14 mol% or less, 2 mol% or more to 13 mol% or less, 2 mol% or more to 12 mol% or less, 2 mol% or more to 11 mol% or more, 2 mol% or more to 10 mol% or less, 2 mol% or more to 9 mol% or less, 2 mol% or more to 8 mol% or less, 2 mol% or more to 7 mol% or less, 2 mol% or more to 6 mol% or less, 2 mol% or more to 5 mol% or less,2 mol% or more to 4 mol% or less, 2 mol% or more to 3 mol% or less, 3 mol% or more to 15 mol% or less, 3 mol% or more to 14 mol% or less, 3 mol% or more to 13 mol% or less, 3 mol% or more to 12 mol% or less, 3 mol% or more to 11 mol% or less, 3 mol% or more to 10 mol% or less, 3 mol% or more to 9 mol% or less, 3 mol% or more to 8 mol% or less, 3 mol% or more to 7 mol% or less, 3 mol% or more to 6 mol% or less, 3 mol% or more to 5 mol% or less %, 3 mol% or more to 4 mol% or less, 4 mol% or more to 15 mol% or less, 4 mol% or more to 14 mol% or less, 4 mol% or more to 13 mol% or less, 4 mol% or more to 12 mol% or less, 4 mol% or more to 11 mol% or less, 4 mol% or more to 10 mol% or less, 4 mol% or more to 9 mol% or less, 4 mol% or more to 8 mol% or less, 4 mol% or more to 7 mol% or less, 4 mol% or more to 6 mol% or less, 4 mol% or more to 5 mol% or less, 5 mol% or more to 15 mol% or less, 5 mol% or more to 14 mol% or less, 5 mol% or more to 13 mol% or less, 5 mol% or more to 12 mol% or less, 5 mol% or more to 11 mol% or less, 5 mol% or more to 10 mol% or less, 5 mol% or more to 9 mol% or less, 5 mol% or more to 8 mol% or less, 5 mol% or more to 7 mol% or less, 5 mol% or more to 6 mol% or less, 6 mol% or more to 15 mol% or less, 6 mol% or more to 14 mol% or less, 6 mol% or more to 13 mol% or less, The ZnO content may be from 6 mol% to 12 mol%, from 6 mol% to 11 mol%, from 6 mol% to 10 mol%, from 6 mol% to 9 mol%, from 6 mol% to 8 mol%, from 6 mol% to 7 mol%, from 7 mol% to 15 mol%, from 7 mol% to 14 mol%, from 7 mol% to 13 mol%, from 7 mol% to 8 mol%, or any and all subranges formed from any of these endpoints. In an embodiment, the precursor glass or glass-ceramic composition may be substantially free of ZnO.

[0185] In embodiments, the precursor glass or glass-ceramic composition may include FeO. Without intending to be bound by theory, it is believed that the addition of FeO may substitute at least a portion of the Mg in the jeffvenite crystal structure with Fe. FeO may also impart color to the precursor glasses and glass-ceramics. In embodiments, the concentration of FeO in the precursor glass or glass ceramic composition may be from 0 mol% or more, e.g., a positive amount, e.g., an amount greater than the inclusion amount (0.05 mol% or more), to 9 mol%, from 0 mol% to 8 mol%, from 0 mol% to 7 mol%, from 0 mol% to 6 mol%, from 0 mol% to 5 mol%, from 0 mol% to 4 mol%, from 0 mol% to 3 mol%, from 0 mol% to 2 mol%, from 0 mol% to 1 mol%, from 1 mol% to 9 mol%, from 2 mol% to 9 mol%, from 3 mol% to 9 mol%, from 4 mol% to 9 mol%, from 5 mol% to 9 mol%, from 6 mol% to 9 mol%, from 7 mol% to 9 mol%, from 8 mol% to 9 mol%, or any and all subranges formed from any of these endpoints. In embodiments, the precursor glass or glass ceramic composition may be substantially free of FeO.

[0186] In embodiments, the precursor glass or glass ceramic composition may include CaO, SrO, or a combination thereof. The addition of CaO, SrO, and combinations thereof may increase the amount of residual glass in the glass ceramic. Without intending to be bound by theory, the inclusion of SrO in the glass ceramic may increase the refractive index of the residual glass to better match the refractive index of the crystalline phase. In an embodiment, the concentration of CaO, SrO, or a combination thereof may be from 0 mol % or more, e.g., a positive amount, e.g., an amount greater than the contamination amount (0.05 mol % or more), to 2.0 mol %, from 0.2 mol % to 2.0 mol %, from 0.4 mol % to 2.0 mol %, from 0.6 mol % to 2.0 mol %, from 0.8 mol % to 2.0 mol %, from 1.0 mol % to 2.0 mol %, from 1.2 mol % to 2.0 mol %, from 1.4 mol % to 2.0 mol %, from 0 mol % to 1.7 mol %, from 0.2 mol % to 1.7 mol %, from 0.4 mol % to 1. In one embodiment, the range may be from 0 to 7 mol%, from 0.6 to 1.7 mol%, from 0.8 to 1.7 mol%, from 1.0 to 1.7 mol%, from 1.2 to 1.7 mol%, from 1.4 to 1.7 mol%, from 0 to 1.4 mol%, from 0 to 1.2 mol%, from 0 to 1.0 mol%, from 0 to 0.8 mol%, from 0 to 0.6 mol%, from 0 to 0.4 mol%, from 0 to 0.2 mol%, or any and all subranges formed from any of these endpoints.In embodiments, the concentration of CaO can be from 0 mol% to 10 mol%, from 1 mol% to 10 mol%, from 2 mol% to 10 mol%, from 3 mol% to 10 mol%, from 4 mol% to 10 mol%, from 5 mol% to 10 mol%, from 6 mol% to 10 mol%, from 7 mol% to 10 mol%, from 8 mol% to 10 mol%, from 9 mol% to 10 mol%, from 0 mol% to 9 mol%, from 0 mol% to 8 mol%, from 0 mol% to 7 mol%, from 0 mol% to 6 mol%, from 0 mol% to 5 mol%, from 0 mol% to 4 mol%, from 0 mol% to 3 mol%, from 0 mol% to 2 mol%, from 0 mol% to 1 mol%, or any and all subranges formed from any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition can be substantially free of CaO. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of SrO. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of both CaO and SrO.

[0187] In embodiments, the precursor glass or glass ceramic composition may include Cs2O. Without intending to be bound by theory, it is believed that the Cs2O additive remains in the residual glass after ceramming and serves to increase the refractive index of the residual glass without causing crystallization. In embodiments, the concentration of Cs2O in the precursor glass or glass ceramic composition may be from 0 mol% or more, e.g., a positive amount, e.g., an amount greater than the inclusion amount (0.05 mol% or more), to 5 mol% or less, 0 mol% or more to 4 mol% or less, 0 mol% or more to 3 mol% or less, 0 mol% or more to 2 mol% or less, 0 mol% or more to 1 mol% or less, 1 mol% or more to 5 mol% or less, 2 mol% or more to 5 mol% or less, 3 mol% or more to 5 mol% or less, 4 mol% or more to 5 mol% or less, or any and all subranges formed from any of these endpoints. In embodiments, the precursor glass or glass ceramic composition may be substantially free of Cs2O.

[0188] In embodiments, the precursor glass or glass ceramic composition may include Li2O. For example, without limitation, the precursor glass or glass ceramic composition may include 3 mol% or less, 2.5 mol% or less, 2 mol% or less, 1.5 mol% or less, 1 mol% or less, 0.7 mol% or less, 0.5 mol% or less, 0.3 mol% or less, or 0.1 mol% or less Li2O, but may include a positive amount, e.g., more than the contaminant amount (0.05 mol% or more), or up to the contaminant amount (i.e., less than 0.05 mol%). In embodiments, the precursor glass or glass ceramic composition may be substantially free of Li2O. Without intending to be bound by theory, when the precursor glass includes 3 mol% or less Li2O, the formation of beta-quartz during heat treatment may be reduced.

[0189] In embodiments, the precursor glass or glass ceramic composition may include Y2O3. Without intending to be bound by theory, Y2O3 may stabilize ZrO2 in the precursor glass or glass ceramic composition. In embodiments, the concentration of Y2O3 may be from 0 mol% or more, e.g., a positive amount, e.g., an amount greater than the amount of contamination (e.g., 0.05 mol% or more), to 2.0 mol%, 0.2 mol% to 2.0 mol%, 0.4 mol% to 2.0 mol%, 0.6 mol% to 2.0 mol%, 0.8 mol% to 2.0 mol%, 1.0 mol% to 2.0 mol%, 1.2 mol% to 2.0 mol%, 1.4 mol% to 2.0 mol%, 1.6 mol% to 2.0 mol%, % to 1.8 mol %, 0 mol % to 1.8 mol %, 0 mol % to 1.6 mol %, 0 mol % to 1.4 mol %, 0 mol % to 1.2 mol %, 0 mol % to 1.0 mol %, 0 mol % to 0.8 mol %, 0 mol % to 0.6 mol %, 0 mol % to 0.4 mol %, 0 mol % to 0.2 mol %, or any and all subranges formed from any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of Y2O3.

[0190] In embodiments, the precursor glass or glass ceramic composition may be substantially free of P2O5. In embodiments, the precursor glass or glass ceramic composition may be free of P2O5. Without intending to be bound by theory, the inclusion of P2O5 in the precursor glass or glass ceramic composition may result in the formation of magnesium phosphate and reduce the formation of a crystalline phase having a jeffvenite crystal structure.

[0191] In embodiments, the precursor glass or glass-ceramic composition may include P2O5. Without intending to be bound by theory, it is believed that the addition of P2O5 may improve the diffusivity of the glass-ceramic composition during the ion-exchange process. In embodiments, the concentration of P2O5 in the precursor glass or glass-ceramic composition can be from 0 mol% or more, e.g., a positive amount, e.g., an amount greater than the inclusion amount (0.05 mol% or more), to 4 mol% or less, from 0 mol% or more to 3.5 mol% or less, from 0 mol% or more to 3 mol% or less, from 0 mol% or more to 2.5 mol% or less, from 0 mol% or more to 2 mol% or less, from 0 mol% or more to 1.5 mol% or less, from 0 mol% or more to 1 mol%, from 0 mol% or more to 0.5 mol% or more to 0.5 mol% or more to 4 mol% or less, from 1 mol% or more to 4 mol% or less, from 1.5 mol% or more to 4 mol% or less, from 2 mol% or more to 4 mol% or less, from 2.5 mol% or more to 4 mol% or less, from 3 mol% or more to 4 mol% or less, from 3.5 mol% or more to 4 mol% or less, or any and all subranges formed from any of these endpoints. In embodiments, the P2O5 contained in the glass-ceramic composition may remain within a residual glass phase of the glass-ceramic composition. The precursor glass or glass-ceramic composition may be substantially free of P2O5.

[0192] In embodiments, the precursor glass or glass-ceramic composition may include MnO2. Without intending to be bound by theory, it is believed that the addition of MnO2 may substitute at least a portion of the Mg in the jeffvenite crystal structure for Mn. MnO2 may also impart color to the precursor glasses and glass-ceramics. For example, and without limitation, the addition of MnO2 may impart a black color to the glass-ceramics. In an embodiment, the concentration of MnO2 is from 0 mol% or more, e.g., a positive amount, e.g., an amount greater than the amount of contamination (0.05 mol% or more) to 10 mol% or less, from 0 mol% or more to 9 mol% or less, from 0 mol% or more to 8 mol% or less, from 0 mol% or more to 7 mol% or less, from 0 mol% or more to 6 mol% or less, from 0 mol% or more to 5 mol% or less, from 0 mol% or more to 4 mol% or less, from 0 mol% or more to 3 mol% or less, from 0 mol% or more to 2 mol% or less, from 0 mol% or more to 1.0 mol% or less, from 0.1 mol% or more to 1 mol% or less, from 0.2 mol% or more to 1.0 mol% or less, from 0.4 mol% or more to 1.0 mol% or less, from 0.6 mol% or more to 1.0 mol% %, 0.8 mol% to 1.0 mol%, 0 mol% to 0.8 mol%, 0 mol% to 0.6 mol%, 0 mol% to 0.4 mol%, 0 mol% to 0.2 mol%, 1 mol% to 10 mol%, 2 mol% to 10 mol%, 3 mol% to 10 mol%, 4 mol% to 10 mol%, 5 mol% to 10 mol%, 6 mol% to 10 mol%, 7 mol% to 10 mol%, 8 mol% to 10 mol%, 9 mol% to 10 mol%, or any and all subranges formed from any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of MnO2.

[0193] In embodiments, the precursor glass or glass ceramic composition may include La2O3. Without intending to be bound by theory, it is believed that the addition of La2O3 may increase the refractive index of the residual glass of the glass-ceramic composition, which may improve the transparency of the glass-ceramic composition. In embodiments, the concentration of La2O3 in the precursor glass or glass-ceramic composition may be from 0 mol% to 7 mol%, from 0 mol% to 6 mol%, from 0 mol% to 5 mol%, from 0 mol% to 4 mol%, from 0 mol% to 3 mol%, from 0 mol% to 2 mol%, from 0 mol% to 1 mol%, from 1 mol% to 7 mol%, from 1 mol% to 6 mol%, from 1 mol% to 5 mol%, from 1 mol% to 4 mol%, from 1 mol% to 3 mol%, from 1 mol% to 2 mol% or more. The La2O3 content may be, for example, 2 mol% to 7 mol%, 2 mol% to 6 mol%, 2 mol% to 5 mol%, 2 mol% to 4 mol%, 2 mol% to 3 mol%, 3 mol% to 7 mol%, 3 mol% to 6 mol%, 3 mol% to 5 mol%, 3 mol% to 4 mol%, 4 mol% to 7 mol%, 4 mol% to 6 mol%, 4 mol% to 5 mol%, 5 mol% to 7 mol%, 5 mol% to 6 mol%, 6 mol% to 7 mol%, or any and all subranges formed from any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of La2O3.

[0194] Articles formed from the precursor glass or glass-ceramic compositions described herein may be of any suitable thickness, depending on the particular application of the glass-ceramic. Glass-ceramic sheet embodiments may have a thickness T of 0.2 mm or more to 10 mm or less. In embodiments, glass-ceramic sheet embodiments may have a thickness T of 6 mm or less, 5 mm or less, 4 mm or less, 3 mm or less, 2 mm or less, 1.0 mm or less, 750 μm or less, 500 μm or less, or 250 μm or less. In embodiments, glass-ceramic sheet embodiments may have a thickness T of 200 μm or more to 5 mm or less, 500 μm or more to 5 mm or less, 200 μm or more to 4 mm or less, 200 μm or more to 2 mm or more, 400 μm or more to 5 mm or less, or 400 μm or more to 2 mm or less. It is contemplated that the thickness of the precursor glass or glass-ceramic article will fall within the subrange formed by any and all of the foregoing endpoints. Alternatively, the glass sheets may be thicker than 10 mm, for example, for certain tempered glass applications or other applications, etc. Alternatively, containers and tubes made from the glasses or glass ceramics disclosed herein may have such thicknesses as wall thicknesses, and, for example, rods and spheres and other articles made from the glasses or glass ceramics disclosed herein may have similar thicknesses.

[0195] In embodiments, the precursor glass or glass ceramic compositions described herein are ion-exchangeable to promote strengthening of the precursor glass or glass ceramic. In a typical ion-exchange process, smaller metal ions in the glass ceramic are replaced or "exchanged" with larger metal ions of the same valence in a layer proximate the outer surface of the glass ceramic. The replacement of smaller ions with larger ions creates compressive stresses in the layer of the glass ceramic. In embodiments, the metal ions are monovalent metal ions (e.g., Li + , Na + , K +ion exchange is accomplished by immersing the glass ceramic in a bath containing at least one molten salt of the larger metal ion that is to replace the smaller metal ion in the glass ceramic. Ion exchange processes used to strengthen the glass ceramic may include, but are not limited to, immersion in a single bath, or immersion in multiple baths of similar or different composition with washing and / or slow cooling steps between immersions. In embodiments, the glass ceramic may be ion exchanged by exposure to molten KNO3 salt, molten NaNO3 salt, or a mixture of molten salts containing KNO3 and NaNO3. If Na2O is present in the precursor glass or glass ceramic, KNO3 may be ion exchanged. + and Na + The ion exchange of LiO may be carried out in a KNO3 salt bath or in a salt bath containing KNO3 with NaNO3. If Li2O is present in the precursor glass or glass-ceramic, Li + and Na +The ion exchange may be performed in a NaNO3 salt bath or a salt bath containing NaNO3 along with KaNO3. In embodiments, the glass-ceramic may be ion-exchanged in a molten salt bath at a bath temperature of from 350° C. to 500° C. For example, without limitation, the glass-ceramic may be ion-exchanged at a bath temperature of from 350° C. to 530° C., from 375° C. to 530° C., from 400° C. to 530° C., from 425° C. to 530° C., from 450° C. to 530° C., from 475° C. to 530° C., from 500° C. to 530° C., from 350° C. to 500° C., from 375° C. to 500° C., from 400° C. to 50 ...00° C. to 500° C., from 400° C. to 500° C., from 400° C. to 500° C., from 400° C. to 500° C., from 400° C. to 500° C., from 400° C. to 500° C., from 400° C. to 500° C., from 400 The ion exchange may be carried out at a bath temperature of 25°C to 500°C, 450°C to 500°C, 475°C to 500°C, 350°C to 475°C, 350°C to 450°C, 350°C to 425°C, 350°C to 400°C, 350°C to 375°C, or any and all subranges formed from any of these endpoints. The ion exchange time may be from 1 hour to 48 hours. In embodiments, the ion exchange process may cause a surface compression layer to develop in the precursor glass or glass-ceramic composition. The development of this surface compression layer is beneficial in achieving better crack resistance and higher flexural strength compared to materials that are not ion exchanged. The surface compression layer provides a higher concentration of exchanged ions in the glass-ceramic article compared to the concentration of exchanged ions in the glass-ceramic article relative to the bulk of the glass-ceramic article (i.e., areas not including surface compression).

[0196] In embodiments, the precursor glass and / or glass ceramic may be ion-exchanged to achieve a compression depth of about 30 μm or more, about 40 μm or more, about 50 μm or more, about 60 μm or more, about 70 μm or more, about 80 μm or more, about 90 μm or more, or about 100 μm or more. In embodiments, the compression depth may be 3% or more of the thickness of the article formed from the precursor glass and / or glass ceramic, 5% or more of the thickness, 10% or more of the thickness, 15% or more of the thickness, 20% or more of the thickness, or even 22% or more of the thickness. The occurrence of this surface compression layer is beneficial in achieving better crack resistance and higher bending strength compared to materials that are not ion-exchanged. The surface compression layer has a higher concentration of exchanged ions in the precursor glass and / or glass ceramic article compared to the concentration of exchanged ions in the article relative to the bulk of the article (i.e., areas not including surface compression).

[0197] In embodiments, the precursor glass and / or glass ceramic is ion-exchanged to achieve a central tension of 10 MPa or greater. In embodiments, the central tension can be 10 MPa or more and 200 MPa or less, 20 MPa or more and 200 MPa or less, 30 MPa or more and 200 MPa or more, 40 MPa or more and 200 MPa or less, 50 MPa or more and 200 MPa or less, 60 MPa or more and 200 MPa or more, 70 MPa or more and 200 MPa or less, 80 MPa or more and 200 MPa or less, 90 MPa or more and 200 MPa or less, 100 MPa or more and 200 MPa or less, 110 MPa or more and 200 MPa or less, 120 MPa or more and 200 MPa or less, 130 MPa or more and 200 MPa or less, 140 MPa or more and 200 MPa or less, 150 MPa or more and 200 MPa or less, 160 MPa or more and 200 MPa or less, 170 MPa or more and 200 MPa or less, 180 MPa or more and 200 MPa or less, 190 MPa or more and 200 MPa or less, or any and all sub-ranges formed from any of these endpoints.

[0198] In an embodiment, the precursor glass or glass ceramic has a pressure of 100 MPa to 1 GPa, 100 MPa to 950 MPa, 100 MPa to 900 MPa, 100 MPa to 850 MPa, 100 MPa to 800 MPa, 100 MPa to 750 MPa, 100 MPa to 700 MPa, 100 MPa to 650 MPa, 100 MPa to 600 MPa, 100 MPa to 550 MPa, 100 MPa to 500 MPa 100MPa or more to 450MPa or less, 100MPa or more to 400MPa or less, 100MPa or more to 350MPa or less, 100MPa or more to 300MPa or less, 100MPa or more to 250MPa or less, 100MPa or more to 200MPa or less, 100MPa or more to 150MPa or less, 150MPa or more to 500MPa or less, 150MPa or more to 450MPa or less, 150MPa or more to 400MPa or less, 150MPa or more to 350MPa or less, 150MPa or more to 300MPa or less, 150MPa or higher to 250MPa or lower, 150MPa or higher to 200MPa or lower, 200MPa or higher to 500MPa or lower, 200MPa or higher to 450MPa or lower, 200MPa or higher to 400MPa or lower, 200MPa or higher to 350MPa or lower, 200MPa or higher to 300MPa or lower, 200MPa or higher to 250MPa or lower, 250MPa or higher to 500MPa or lower, 250MPa or higher to 450MPa or lower, 250MPa or higher to 400MPa or lower, 250MPa or higher to 350MPa or lower, 250MPa or higher to 300MPa , 300 MPa to 500 MPa, 300 MPa or more to 450 MPa or less, 300 MPa or more to 400 MPa or less, 300 MPa or more to 350 MPa or less, 350 MPa to 500 MPa or less, 350 MPa or more to 450 MPa or less, 350 MPa or more to 400 MPa or less, 400 MPa or more to 500 MPa or less, 400 MPa or more to 450 MPa or less, 450 MPa or more to 500 MPa or less, or any and all sub-ranges formed from any of these endpoints.In embodiments, the precursor glass or glass ceramic can have a surface compressive stress of about 100 MPa or greater, about 150 MPa or greater, about 200 MPa or greater, about 250 MPa or greater, about 300 MPa or greater, about 350 MPa or greater, about 400 MPa or greater, about 450 MPa or greater, or about 500 MPa or greater.

[0199] In embodiments, the process for making a glass-ceramic includes melting a batch of components to form a precursor glass. This molten precursor glass may be poured into a mold. In embodiments, the mold may be made of steel. The precursor glass may be slowly cooled. The precursor glass pack may be cut and then heat treated to form a glass-ceramic.

[0200] Alternatively, the precursor glasses described herein can be produced from molten precursor glasses and formed into sheets by processes including, but not limited to, slot draw, float, rolling, and other sheet forming methods known in the art.

[0201] In an embodiment, the process of making a glass-ceramic includes heat treating (also referred to herein as "ceramming") a precursor glass at one or more preselected temperatures for one or more preselected times to induce homogenization of the glass and crystallization (i.e., nucleation and growth) of one or more crystalline phases (e.g., having one or more compositions, amounts, morphologies, sizes or size distributions, etc.). The one or more preselected temperatures may be less than 1500K throughout the heat treatment process. It should be noted that temperature refers to a range of temperatures and not necessarily one static temperature. Similarly, it should be noted that crystal nucleation and / or growth may occur over a series or multiple separate heat treatments that are joined together to achieve the desired crystal growth. Without intending to be bound by theory, the nucleating agent may act as or form nucleation sites at which nucleation and growth of particles of a crystalline phase occurs, including nucleation and growth of particles of a crystalline phase having a jeffvenite crystal structure. The nucleation sites are positioned and oriented within the precursor glass such that particles of the resulting crystalline phase, including particles of a crystalline phase having a jeffvenite crystal structure, are uniformly distributed throughout the resulting glass-ceramic and grow with random orientation, resulting in a glass-ceramic with isotropic material properties. In an embodiment, the heat treatment may include heating the precursor glass in a heat treatment furnace at a rate of 1-10°C / min until the furnace reaches a first temperature. The first temperature of the furnace may be from 700°C or more to 950°C or less.In an embodiment, the first temperature of the furnace is 700° C. to 950° C., 710° C. to 950° C., 730° C. to 950° C., 750° C. to 950° C., 770° C. to 950° C., 790° C. to 950° C., 810° C. to 950° C., 830° C. to 950° C., 850° C. to 950° C., 870° C. to 950° C., 890° C. to 950° C., 910° C. to 950° C., 930° C. to 950° C., 700° C. to 950° C., The temperature may be from 700°C to 930°C, 700°C to 910°C, 700°C to 890°C, 700°C to 870°C, 700°C to 850°C, 700°C to 830°C, 700°C to 810°C, 700°C to 790°C, 700°C to 770°C, 700°C to 750°C, 700°C to 730°C, 700°C to 710°C, or any and all subranges formed from any of these endpoints. Unless otherwise specified, the temperature of the heat treatment or ion exchange treatment refers to the temperature of the environment to which the article is exposed (such as a furnace for heat treatment or a molten salt bath for ion exchange treatment). In an embodiment, the process for producing a glass-ceramic includes maintaining the precursor glass at a first temperature for a first time period ranging from 0.25 hours to 6 hours.For example, without limitation, the precursor glass may be cured for 0.25 hours to 6 hours, 0.5 hours to 6 hours, 0.75 hours to 6 hours, 1 hour to 6 hours, 1.25 hours to 6 hours, 1.5 hours to 6 hours, 1.75 hours to 6 hours, 2 hours to 6 hours, 2.25 hours to 6 hours, 2.5 hours to 6 hours, 2.75 hours to 6 hours, 3 hours or more to less than 6 hours, 3.25 hours or more to less than 6 hours, 3.5 hours or more to less than 6 hours, 3.75 hours or more to less than 6 hours, 4 hours or more to less than 6 hours, 4.25 hours or more to less than 6 hours, 4.5 hours or more to less than 6 hours, 4.75 hours or more to less than 6 hours, 5 hours or more to less than 6 hours, 5.25 hours or more to less than 6 hours, 5.5 hours or more to less than 6 hours, 5.75 hours or more to less than 6 hours, 0.25 hours or more to 5 .75 hours or less, 0.25 hours or more to 5.5 hours or less, 0.25 hours or more to 5.25 hours or more, 0.25 hours or more to 5 hours or less, 0.25 hours or more to 4.75 hours or less, 0.25 hours or more to 4.5 hours or less, 0.25 hours or more to 4.25 hours or more, 0.25 hours or more to 4 hours or less, 0.25 hours or more to 3.75 hours or less, 0.25 hours or more to 3.5 hours or less, 0.25 hours or more to 3.25 hours or more The precursor glass may be maintained at the first temperature for a first time period ranging from 0.25 to 3 hours, 0.25 to 2.75 hours, 0.25 to 2.5 hours, 0.25 to 1 hour, 0.25 to 0.75 hours, 0.25 to 0.5 hours, or any and all subranges formed from any of these endpoints. In embodiments, heat treating the precursor glass in a heat treatment furnace at the first temperature for a first time period may promote both nucleation and growth of desired crystalline phases in the precursor glass to form a glass ceramic. In other embodiments, heat treating the precursor glass in a heat treatment furnace at the first temperature for a first time period may promote nucleation of desired crystalline phases in the precursor glass, and a second heat treatment step is performed to grow the nucleated crystalline phases in the precursor glass to form a glass ceramic.

[0202] For example, in an embodiment, the heat treatment may include a second step of heating the precursor glass in a heat treatment furnace at a rate of 1-10°C / min until the furnace reaches a second temperature. The second temperature may be different from the first temperature. The second temperature of the furnace may be 750°C to 950°C. In an embodiment, the second temperature may be 750°C to 950°C, 770°C to 950°C, 790°C to 950°C, 810°C to 950°C, 830°C to 950°C, 850°C to 950°C, 870°C to 950°C, 890°C to 950°C, 910°C to 950°C, 930°C to 950°C, 7 ...50°C to 950°C, 850°C to 95 The second temperature may be from 0.25 to 6 hours, inclusive. In one embodiment, the process for making a glass-ceramic includes maintaining the precursor glass at the second temperature for a second period of time ranging from 0.25 to 6 hours, inclusive. In another ...For example, without limitation, the precursor glass may be cured for 0.25 hours to 6 hours, 0.5 hours to 6 hours, 0.75 hours to 6 hours, 1 hour to 6 hours, 1.25 hours to 6 hours, 1.5 hours to 6 hours, 1.75 hours to 6 hours, 2 hours to 6 hours, 2.25 hours to 6 hours, 2.5 hours to 6 hours, 2.75 hours to 6 hours, 3 hours or more to less than 6 hours, 3.25 hours or more to less than 6 hours, 3.5 hours or more to less than 6 hours, 3.75 hours or more to less than 6 hours, 4 hours or more to less than 6 hours, 4.25 hours or more to less than 6 hours, 4.5 hours or more to less than 6 hours, 4.75 hours or more to less than 6 hours, 5 hours or more to less than 6 hours, 5.25 hours or more to less than 6 hours, 5.5 hours or more to less than 6 hours, 5.75 hours or more to less than 6 hours, 0.25 hours or more to 5 .75 hours or less, 0.25 hours or more to 5.5 hours or less, 0.25 hours or more to 5.25 hours or more, 0.25 hours or more to 5 hours or less, 0.25 hours or more to 4.75 hours or less, 0.25 hours or more to 4.5 hours or less, 0.25 hours or more to 4.25 hours or more, 0.25 hours or more to 4 hours or less, 0.25 hours or more to 3.75 hours or less, 0.25 hours or more to 3.5 hours or less, 0.25 hours or more to 3.25 hours or more The precursor glass may be maintained at the second temperature for a second time in the range of 0.25 to 3 hours, 0.25 to 2.75 hours, 0.25 to 2.5 hours, 0.25 to 2.25 hours, 0.25 to 1 hour, 0.25 to 0.75 hours, 0.25 to 0.5 hours, or any and all subranges formed from any of these endpoints. Heat treating the precursor glass having the nucleated crystalline phase in the heat treatment furnace at the second temperature for a second time grows the desired crystalline phase in the precursor glass to form a glass-ceramic.

[0203] In embodiments, the step of heat treating the precursor glass may further include heating the precursor glass in a heat treatment furnace to one or more subsequent furnace temperatures, such as from 750° C. to 950° C., and holding the precursor glass at each subsequent furnace temperature for a range of time, such as from 0.25 hours to 6 hours.

[0204] In embodiments, the heat treatment of the precursor glass may be carried out at ambient pressure. In embodiments, the heat treatment of the precursor glass may be carried out at ambient atmospheric pressure (e.g., 101.325 kPa). In embodiments, the heat treatment of the precursor glass may be carried out at about 100 kPa. In one or more embodiments, the heat treatment of the precursor glass may be carried out at a pressure of 15 GPa or less. For example, without limitation, the heat treatment of the precursor glass may be carried out at a pressure of 15 GPa or less, 10 GPa or less, 5 GPa or less, or 1 GPa or less. According to the methods described herein, jeffvenite may be formed in the glass-ceramic article without the need for such pressurization.

[0205] After heat treatment (i.e., after nucleation and growth of the crystalline phase within the precursor glass), at least some of the grains of the crystalline phase having the jeffvenite crystal structure overlap and interlock with one another within the residual glass phase. The grains of the crystalline phase having the jeffvenite crystal structure are such that the glass-ceramic has a viscosity of about 0.75 MPa m 1 / 2 or other such values ​​as disclosed herein. In other aspects of the present disclosure, overlapping and interdigitation of the jeffvenite crystal structure occurs within the glass-ceramic of the body, but to an extent that does not provide such fracture toughness. In yet other aspects, crystals of the jeffvenite crystal structure may be present, but are sparse such that they do not overlap or interdigitate with each other to any extent within the glass-ceramic of the body.

[0206] In embodiments, the resulting glass-ceramic may be transparent, translucent, or opaque. In embodiments, the glass-ceramic has an average transmission of 85% or more of light over a wavelength range of about 400 nm to about 1000 nm at an article thickness of 0.85 mm. In embodiments, the average transmission of the glass-ceramic is about 85% or more, about 86% or more, about 87% or more, about 88% or more, about 89% or more, about 90% or more, about 91% or more, about 92% or more, about 93% or more of light over a wavelength range of about 400 nm to about 1000 nm at an article thickness of 0.85 mm.

[0207] In embodiments, the resulting glass-ceramic may be colored. The colored glass-ceramic article may include at least one colorant of a colorant package that functions to impart a desired color to the glass-ceramic. The colorant package may include at least one of Au, Ag, Cr2O3, transition metal oxides (e.g., CuO, NiO, Co3O4, TiO2, Cr2O3), rare earth metal oxides (e.g., CeO2), and / or combinations thereof as colorants in the colorant package, and the precursor glass or glass-ceramic may include at least one of 1×10 -6 % or more, e.g., greater than 0.0005 mol%, e.g., greater than 0.001 mol%, e.g., greater than 0.01 mol%, e.g., greater than 0.1 mol%, e.g., greater than 0.2 mol%, e.g., greater than 0.01 mol%, and / or 10 mol% or less (i.e., the sum of all colorants in the colorant package), e.g., less than 5 mol%, e.g., less than 2 mol%, e.g., less than 1 mol%, e.g., less than 0.5 mol%, e.g., in some cases less than 0.25 mol% of colorants. For example, consistent with the disclosure of U.S. Patent Application No. 17 / 691,813, a yellow glass or glass-ceramic may contain rare earth metal oxides in amounts of greater than about 0.2 mol% and less than 1 mol%, e.g., a black or gray glass may contain NiO and Co3O4 in such amounts; a green glass or glass-ceramic may similarly contain Cr2O3; a pink, red, or orange glass or glass-ceramic may contain rare earth metal oxides in amounts of greater than about 1×10 -6The glass may contain small amounts of gold, such as more than 0.5 mole percent and less than 0.5 mole percent. Other colorants may be used in such amounts as well, such as iron oxide for green or brown glass or glass ceramic, manganese oxide for amber or purple, selenium for red, antimony for white, uranium for fiery colors, copper for red, tin for white, lead for yellow, and other colorants. However, some of such colorants, such as lead, antimony, and selenium, may be less desirable than others. Further oxidation-reduction of colorants, ultraviolet light treatment, and particulates may contribute to the color of the glass, and the applicant hereby incorporates by reference in its entirety U.S. Provisional Patent Application No. 63 / 433060, filed December 16, 2022, U.S. Provisional Patent Application No. 63 / 433065, filed December 16, 2022, and U.S. Provisional Patent Application No. 63 / 433119, filed December 16, 2022.

[0208] In embodiments, the colored glass-ceramics may form glass-ceramic sheets. The colored glass-ceramics may be colored at some, most, and / or all frequencies in the visible spectrum (e.g., above 4×10) at thicknesses disclosed herein. 14 From 8×10 14 Hz; wavelengths from 380 to 750 nanometers) and may be semi-transparent (e.g., total transmission greater than 1%, greater than 5%, greater than 10%, and / or less than 95%, less than 92%, less than 90%, less than 85%, less than 80%, less than 70%). Additionally, the total transmission of at least one 10 nm wide band within the wavelength range of 380 nm to 750 nm (e.g., 380 to 390 nm, 390 to 400 nm, 385 to 395 nm, and / or 740 to 750 nm) through the sheet of glass at a base thickness (e.g., about 1 mm, about 0.6 mm, about 0.8 mm, about 1.2 mm, about 1.6 mm, about 2 mm, where about in this context refers to within 0.2 mm) is less than 90%, e.g., less than 85%, less than 80%, less than 70%, less than 60%, and / or less than 50%.

[0209] In embodiments, the colored glass-ceramics can be opaque, such as solid colors (e.g., white, black, dark green) that are substantially not transparent to visible light (e.g., less than 1% total transmittance at wavelengths from 380 to 750 nanometers). The colored glass-ceramics can be transparent to some, most, and / or all frequencies in the visible spectrum (e.g., above 4×10 14 From 8×10 14 Hz; wavelengths from 380 to 750 nanometers), may be translucent, such as having a transmittance of greater than 95%, greater than 96%, and / or less than 100%.

[0210] In an embodiment, the color of the glass-ceramic is determined by the CIELAB color space coordinates L * , a * , and b * In some embodiments, L * The value of L can be from 0 to 100, 10 to 100, 20 to 100, 30 to 100, 40 to 100, 50 to 100, 60 to 100, 70 to 100, 80 to 100, 90 to 100, 0 to 90, 0 to 80, 0 to 70, 0 to 60, 0 to 50, 0 to 40, 0 to 30, 0 to 20, 0 to 10, or any and all subranges formed from any of these endpoints. * The coordinates may be 50 or more, 60 or more, 70 or more, 80 or more, and 100 or less. * The value of may be -128 to 128, -120 to 128, -110 to 128, -100 to 128, -90 to 128, -80 to 128, -70 to 128, -60 to 128, -50 to 128, -40 to 128, -30 to 128, -20 to 128, -10 to 128, 0 to 128, 10 to 128, 20 to 128, 30 to 128, 40 to 128, 50 to 128, 60 to 128, 70 to 128, 80 to 128, 90 to 128, 100 to 128, 110 to 128, 120 to 128, or any and all subranges formed from any of these endpoints. *The coordinates may be greater than or equal to -100, greater than or equal to -90, greater than or equal to -80, greater than or equal to -70, greater than or equal to -60, greater than or equal to -50, greater than or equal to -40, greater than or equal to -30, or greater than or equal to -20. * The coordinate may be 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, or 20 or less. * The value of b may be -128 to 128, -120 to 128, -110 to 128, -100 to 128, -90 to 128, -80 to 128, -70 to 128, -60 to 128, -50 to 128, -40 to 128, -30 to 128, -20 to 128, -10 to 128, 0 to 128, 10 to 128, 20 to 128, 30 to 128, 40 to 128, 50 to 128, 60 to 128, 70 to 128, 80 to 128, 90 to 128, 100 to 128, 110 to 128, 120 to 128, or any and all subranges formed from any of these endpoints. * The coordinates may be -100 or greater, -90 or greater, -80 or greater, -70 or greater, -60 or greater, -50 or greater, -40 or greater, -30 or greater, or -20 or greater. * The coordinates may be 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, or 20 or less.

[0211] In an embodiment, the resulting glass ceramic has a density of 2.65 g / cm 3 From the above, 2.95g / cm 3 In an embodiment, the resulting glass-ceramic may have a density of 2.50 g / cm 3 From the above, 3.70g / cm 3 For example, and without limitation, glass ceramics may have a density of 2.50 g / cm 3 From the above, 3.70g / cm 3 Below 2.55g / cm 3 From the above, 3.70g / cm 3 Below 2.60g / cm 3From the above, 3.70g / cm 3 Below 2.65g / cm 3 From the above, 3.70g / cm 3 Below 2.70g / cm 3 From the above, 3.70g / cm 3 Below 2.75g / cm 3 From the above, 3.70g / cm 3 Below 2.80g / cm 3 From the above, 3.70g / cm 3 Below, 2.85g / cm 3 From the above, 3.70g / cm 3 Below, 2.90g / cm 3 From the above, 3.70g / cm 3 Below 3.00g / cm 3 From the above, 3.70g / cm 3 Below, 3.10g / cm 3 From the above, 3.70g / cm 3 Below, 3.20g / cm 3 From the above, 3.70g / cm 3 Below, 3.30g / cm 3 From the above, 3.70g / cm 3 Below, 3.40g / cm 3 From the above, 3.70g / cm 3 Below 2.50g / cm 3 From the above, 3.60g / cm 3 Below 2.55g / cm 3 From the above, 3.60g / cm 3 Below 2.60g / cm 3 From the above, 3.60g / cm 3 Below 2.65g / cm 3 From the above, 3.60g / cm 3 Below 2.70g / cm 3 From the above, 3.60g / cm 3 Below 2.75g / cm 3 From the above, 3.60g / cm 3 Below 2.80g / cm 3 From the above, 3.60g / cm 3 Below, 2.85g / cm 3 From the above, 3.60g / cm 3 Below, 2.90g / cm 3 From the above, 3.60g / cm3 Below 3.00g / cm 3 From the above, 3.60g / cm 3 Below, 3.10g / cm 3 From the above, 3.60g / cm 3 Below, 3.20g / cm 3 From the above, 3.60g / cm 3 Below, 3.30g / cm 3 From the above, 3.60g / cm 3 Below, 3.40g / cm 3 From the above, 3.60g / cm 3 Below 2.65g / cm 3 From the above, 2.95g / cm 3 Below 2.70g / cm 3 From the above, 2.95g / cm 3 Below 2.75g / cm 3 From the above, 2.95g / cm 3 Below 2.80g / cm 3 From the above, 2.95g / cm 3 Below, 2.85g / cm 3 From the above, 2.95g / cm 3 Below, 2.90g / cm 3 From the above, 2.95g / cm 3 Below 2.75g / cm 3 From the above, 2.90g / cm 3 Below 2.75g / cm 3 From the above, 2.85g / cm 3 Below 2.75g / cm 3 From the above, 2.80g / cm 3 The glass-ceramic article may have a density between 0.1 and 0.25, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, 13.0, 14.0, 15.0, 16.0, 17.0, 18.0, 19.0, 20.0, 21.0, 22.0, 23.0, 24.0, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0, 50.0, 51.0, 52.0, 53.0, 54.0, 55.0, 56.0, 57.0, 58.0, 59.0, 60.0, 61.0, 62.0, 63.0, 64.0, 65.0, 66.0, 67.0, 68.0, 69.0, 70.0, 71.0, 72.0, 73.0, 74.0, 75.0, 76.0, 77.0, 78.0, 79.0, 80

[0212] In embodiments, the resulting glass-ceramic may include a crystalline phase having a jeffvenite crystal structure. In embodiments, at least some, or even most, of the grains of the crystalline phase having the jeffvenite crystal structure in the glass-ceramic may have a dimension (e.g., as measured from a cross-section / polished cut of the glass-ceramic, where "dimension" is a linear cross-sectional dimension, such as the longest cross-sectional dimension, shortest cross-sectional dimension, average cross-sectional dimension, etc., measured from the opposite outermost surfaces of the grain through the geometric center of the grain along the surface of the cross-section / polished cut of the glass-ceramic; unless otherwise specified, "dimension" in this context refers to the longest such cross-sectional dimension for a given grain; see the grains depicted in Figures 3-4, 6A-6F, and generally in Figure 9) that is smaller than a wavelength of visible light. For example, without limitation, at least some of the grains, or even the majority of the grains, of a crystalline phase having a jeffvenite crystal structure may have dimensions of 500 nm or less, 400 nm or less, 350 nm or less, 300 nm or less, 250 nm or less, 200 nm or less, 150 nm or less, or even 100 nm or less. In embodiments, at least some of the grains, or even the majority of the grains, of a crystalline phase having a jeffvenite crystal structure in the glass-ceramic may have dimensions of 20 nm or more, or even 30 nm or more.For example, without limitation, at least some of the grains, or even the majority of the grains, of a crystalline phase having a jeffvenite crystal structure in the glass-ceramic may be 20 nm to 100 nm, 30 nm to 100 nm, 40 nm to 100 nm, 50 nm to 100 nm, 60 nm to 100 nm, 70 nm to 100 nm, 80 nm to 100 nm, 90 nm to 100 nm, 20 nm to 9 ...100 nm to 100 nm, 100 nm to 100 nm, 100 nm to 100 nm, 100 nm to 100 nm, 100 nm to 100 nm, 100 nm to 100 nm, 100 nm to 100 nm, 100 nm to 100 nm, 100 nm to 100 nm, 100 nm to 10 The particles may have dimensions of 0 to 90 nm, 20 to 80 nm, 30 to 80 nm, 20 to 70 nm, 30 to 70 nm, 20 to 60 nm, 30 to 60 nm, 20 to 50 nm, 30 to 50 nm, 20 to 40 nm, 30 to 40 nm, or any and all subranges formed from any of these endpoints. In embodiments, at least some of the particles of the crystalline phase having the jeffvenite crystal structure may be elongated in shape. In embodiments, at least some of the particles of the crystalline phase having the jeffvenite crystal structure may have a needle-like or plate-like shape. In embodiments, the particles of the crystalline phase having the jeffvenite crystal structure may have a bulk elastic modulus of about 170 GPa. In embodiments, the particles of the crystalline phase having the jeffvenite crystal structure may have a hardness of about 1350 VHn.

[0213] In embodiments, the resulting glass-ceramic may include a phase assemblage, in which at least some, or even most of the particles of the crystalline phases in the phase assemblage have dimensions smaller than the wavelength of visible light. For example, without limitation, at least some, or even most of the particles of the crystalline phases in the phase assemblage may have dimensions of 500 nm or less, 400 nm or less, 350 nm or less, 300 nm or less, 250 nm or less, 200 nm or less, 150 nm or less, or even 100 nm or less. In embodiments, at least some, or even most of the particles of the crystalline phases in the phase assemblage may have dimensions of 20 nm or more, or even 30 nm or more. For example, without limitation, at least some, or even a majority, of the grains of the crystalline phase in the glass-ceramic may be 20 nm to 100 nm, 30 nm to 100 nm, 40 nm to 100 nm, 50 nm to 100 nm, 60 nm to 100 nm, 70 nm to 100 nm, 80 nm to 100 nm, 90 nm to 100 nm, 20 nm to 90 nm, 30 nm to 90 nm, nm or less, 20 nm to 80 nm, 30 nm to 80 nm, 20 nm to 70 nm, 30 nm to 70 nm, 20 nm to 60 nm, 30 nm to 60 nm, 20 nm to 50 nm, 30 nm to 50 nm, 20 nm to 40 nm, 30 nm to 40 nm, or any and all subranges formed from any of these endpoints.

[0214] In embodiments, the glass ceramic may have an elastic modulus of 50 GPa or more and 200 GPa or less. In embodiments, the glass ceramic may have an elastic modulus of 50 GPa or more, 80 GPa or more, 90 GPa or more, or even 100 GPa or more. In embodiments, the glass ceramic may have an elastic modulus of 200 GPa or less, or even 150 GPa or less. In embodiments, the glass ceramic may have an elastic modulus of 50 GPa or more and 200 GPa or less, 50 GPa or more and 175 GPa or more, 60 GPa or more and 175 GPa or more, 60 GPa or more and 150 GPa or less, 70 GPa or more and 175 GPa or more, 70 GPa or more and 150 GPa or less, 80 GPa or more and 175 GPa or more, or even 80 GPa or more and 150 GPa or less, or any and all subranges formed from any of these endpoints.

[0215] In an embodiment, the glass-ceramic has a hardness of about 0.75 MPa m 1 / 2 Approximately 0.85MPa m 1 / 2 Approximately 1.0MPa m 1 / 2 Approximately 1.1MPa m 1 / 2 More than 1.2MPa m 1 / 2 More than 1.3MPa m 1 / 2 More than 1.4MPa m 1 / 2 More than 1.5MPa m 1 / 2 More than 1.6MPa m 1 / 2 More than 1.7MPa m 1 / 2 More than 1.8MPa m 1 / 2 More than 1.9MPa m 1 / 2 or more, or approximately 2.0 MPa m 1 / 2 In one embodiment, the fracture toughness is 0.75 MPa m 1 / 2 Above 2MPa m 1 / 2 The ranges below, or any and all subranges formed from any of these endpoints.

[0216] In one or more embodiments, the glass-ceramics have high crack and scratch resistance by exhibiting a Vickers hardness of 600 kgf / mm. 2 (approx. 5880N / m 2 ) or more than 1400kgf / mm 2 (approx. 13720N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) or more than 1300kgf / mm 2 (approx. 12740N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) or more than 1200kgf / mm 2 (approx. 11760N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) or more than 1100kgf / mm 2 (approx. 10780N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) above 1000kgf / mm 2 (approx. 9800N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) above 900kgf / mm 2 (about 8820N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) or more than 875kgf / mm 2 (about 8575N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) or more than 850kgf / mm 2 (about 8330N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) or more than 825kgf / mm 2 (about 8085N / m 2 ) or less, 600kgf / mm 2(approx. 5880N / m 2 ) above 800kgf / mm 2 (approx. 7840N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) or more than 775kgf / mm 2 (approx. 7595N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) or more than 750kgf / mm 2 (approx. 7350N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) or more than 725kgf / mm 2 (approx. 7105N / m 2 ) or less, 600kgf / mm 2 (approx. 5880N / m 2 ) above 700kgf / mm 2 (Approx. 6860N / m 2 ) or less, 700kgf / mm 2 (Approx. 6860N / m 2 ) above 900kgf / mm 2 (about 8820N / m 2 ) or less, 700kgf / mm 2 (Approx. 6860N / m 2 ) or more than 875kgf / mm 2 (about 8575N / m 2 ) or less, 700kgf / mm 2 (Approx. 6860N / m 2 ) or more than 850kgf / mm 2 (about 8330N / m 2 ) or less, 700kgf / mm 2 (Approx. 6860N / m 2 ) or more than 825kgf / mm 2 (about 8085N / m 2 ) or less, or 700kgf / mm 2 (Approx. 6860N / m 2 ) above 800kgf / mm 2 (approx. 7840N / m 2 In some embodiments, the Vickers hardness is in the range of 600 kgf / mm2 (approx. 5880N / m 2 ) or more, 625kgf / mm 2 (Approx. 6125N / m 2 ) or more, 650kgf / mm 2 (Approx. 6370N / m 2 ) or more, 675kgf / mm 2 (Approx. 6615N / m 2 ) or more, 700kgf / mm 2 (Approx. 6860N / m 2 ) or more, 725kgf / mm 2 (approx. 7105N / m 2 ) or more, 750kgf / mm 2 (approx. 7350N / m 2 ) or more, 775kgf / mm 2 (approx. 7595N / m 2 ) or more, 800kgf / mm 2 (approx. 7840N / m 2 ) or more, 825kgf / mm 2 (about 8085N / m 2 ) or more, 850kgf / mm 2 (about 8330N / m 2 ) or more, 875kgf / mm 2 (about 8575N / m 2 ) or more, or 900kgf / mm 2 (about 8820N / m 2 ), or any and all subranges formed from any of these endpoints.

[0217] The resulting glass-ceramic may be provided as a sheet, which may then be reshaped or reformed into a curved or bent piece of uniform thickness by rolling, blowing, bending, sagging, vacuum forming, or other means. The reshaping may occur prior to heat treatment, or the forming step may also function as a heat treatment step, where both forming and heat treatment occur substantially simultaneously.

[0218] The glass ceramics and glass ceramic articles described herein may be used in a variety of applications, including, for example, cover glass or glass backplane applications in consumer or commercial electronic devices, including LCD and LED displays, computer monitors, and automated teller machines (ATMs); touch panel or tactile sensor applications for portable electronic devices, including, for example, mobile phones, personal media players, and tablet computers; integrated circuit applications, including, for example, semiconductor wafers; solar cell applications; architectural glass applications; automotive or vehicle glass applications; or commercial or household appliance applications. In embodiments, consumer electronic devices (e.g., smartphones, tablet computers, personal computers, ultrabooks, televisions, and cameras), architectural glass, and / or automotive glass may comprise the glass articles described herein.

[0219] An example electronic device incorporating any of the glass-ceramic articles disclosed herein is shown in Figures 1 and 2. Specifically, Figures 1 and 2 show a consumer electronic device 100 including a housing 102 having a front surface 104, a back surface 106, and sides 108; electrical components (not shown) at least partially within or entirely within the housing, including at least a controller, memory, and a display 110 at or adjacent the front surface of the housing; and a cover substrate 112 at or on the front surface of the housing to cover the display. In an embodiment, at least a portion of at least one of the cover substrate 112 and the housing 102 may include any of the glass-ceramic articles disclosed herein.

[0220] 8A and 8B, an embodiment of a glass-ceramic article 200 formed from a glass-ceramic disclosed herein is shown. In this embodiment, the glass-ceramic article may be in the form of a glass sheet and may include a body 201 disposed between a first side 202 and an opposing second side 204. The body 201 may include, or consist essentially of, a glass-ceramic as described herein. The first side 202 and the second side 204 may be major sides of the glass sheet that face away from one another. In an embodiment, the first side 202 and the second side 204 may be substantially planar and spaced apart from one another by a thickness T defined between the first side 202 and the second side 204. The first side 202 and the second side 204 are defined by at least one edge surface 206 that forms a perimeter that generally defines the shape of the glass-ceramic article 200. In the embodiment shown in FIGS. 8A and 8B, the glass-ceramic article is rectangular in shape and has a length L and a width W. In this embodiment, the width W of the glass sheet is defined as the distance between the opposing edges along the first surface 202 perpendicular to the thickness T. The length L is defined as the distance between the opposing edges along the first surface 202 perpendicular to the thickness T and width W. In embodiments, the width W can be greater than or equal to the thickness T, and the length L can be greater than or equal to the width W. However, it should be understood that other shapes of the glass-ceramic article are contemplated and possible, including, without limitation, squares, circles, and other regular or irregular geometric shapes. For example, the glass-ceramic article can include rods, fibers, boules, curved sheets, tubes, bowls, lenses, vials, bottles, or other containers.

[0221] In embodiments, the thickness T of the glass-ceramic article 200 may be described herein. The length L and width W of the glass-ceramic article may be selected according to the particular application for which the glass-ceramic article 200 is utilized. In embodiments, the length L and width W of the glass-ceramic article may be 5 mm or greater, e.g., 10 mm or greater, 15 mm or greater, 20 mm or greater, 25 mm or greater, and 30 mm or greater. For example, without limitation, the length L of the glass-ceramic article may be from 30 mm to 1 m, from 30 mm to 75 cm, from 30 mm to 50 cm, from 30 mm to 25 cm, from 30 mm to 20 cm, from 30 mm to 15 cm, from 30 mm to 10 cm, from 30 mm to 5 cm, or any and all subranges formed from any of these endpoints. The width W of the glass-ceramic article can be from 30 mm to 1 m, from 30 mm to 75 cm, from 30 mm to 50 cm, from 30 mm to 25 cm, from 30 mm to 20 cm, from 30 mm to 15 cm, from 30 mm to 10 cm, from 30 mm to 5 cm, or any and all subranges formed from any of these endpoints. In embodiments where the glass-ceramic article is a glass sheet, as shown in Figures 8A and 8B, the surface of the glass sheet is 25 mm 2 In embodiments where the glass-ceramic article is a glass sheet, the glass-ceramic in the body 201 of the glass sheet may have an area of ​​25 mm 3 It may have a volume of more than 10 ...

[0222] In an embodiment, the body 201 of the glass-ceramic article 200 has an average transmission of at least 75% for light in the wavelength range of 400 nm to 800 nm (endpoints included) at an article thickness of 0.85 mm such that the glass-ceramic article is transparent. In an embodiment, the body 201 of the glass-ceramic article 200 has an average transmission of 20% or more and less than 75% for light in the wavelength range of 400 nm to 800 nm (endpoints included) at an article thickness of 0.85 mm such that the glass-ceramic article is translucent. In an embodiment, the body of the glass-ceramic article has an average transmission of less than 20% measured at normal incidence for light in the wavelength range of 400 nm to 800 nm (endpoints included) at an article thickness of 0.85 mm such that the glass-ceramic article is opaque. In an embodiment, the body 201 of the glass-ceramic article 200 is at least partially translucent such that at least 20% of light having wavelengths between 400 nm and 800 nm directed into the thickness of the article is transmitted through the body.

[0223] Jeff Benite characterization method In an embodiment, the glass-ceramic article may be tested by X-ray diffraction to determine whether the glass-ceramic article comprises the jeffvenite crystal structure, as described in detail herein, using the following equipment and software: X-ray diffractometer - Bruker-AXSD8 Endeavor with Cu radiation and Lynx Eye detector, Rocklabs Whisper Series Ring Mill, backfill sample holder (Malvern Panalytical PW1770 / 10 Powder Sample Preparation Kit and PW18XX sample holder), 6 inch by 6 inch (about 15 cm by about 15 cm) measuring paper, glass slides, spatula, and data analysis software (MDI Jade, Bruker Topas, and Powder Diffraction File Database PDF-4).

[0224] A sample of the glass-ceramic article is received as a small piece of glass-ceramic. The glass-ceramic small piece is crushed in a ring mill to obtain about 3 grams of glass-ceramic. The 3 grams of the glass-ceramic sample is ground into a fine powder using a Rocklabs ring mill for a period of about 30 seconds.

[0225] Fill a PW18XX sample holder with the fine powder described herein. Fix the sample holder ring to the bench. Spread the fine powder within the sample holder ring so that the fine powder is heaped in a cone shape within the holder ring. Use a glass slide to firmly press the fine powder into the holder ring. Use the glass slide to scrape any excess powder back into the holder ring. Additional fine powder may be added as necessary to fill the sample holder. This process is repeated until a tightly packed powder specimen is obtained. Remove excess fine powder beyond the edge of the holder ring using the edge of the glass slide. Place the base plate on the holder ring and fix in place. Remove the complete sample holder from the bench and load into the X-ray diffractometer.

[0226] A job file for the sample is created in XRD Commander. The job file contains the sample's location in the XRD diffractometer and the sample's identification information. After the job file is created, the XRD diffractometer scans the sample.

[0227] After the sample is scanned with the X-ray diffractometer, the data from the X-ray diffractometer is analyzed using MDI Jade software. The file containing the data from the X-ray diffractometer is opened in MDI Jade. The "Phases" window is used to identify signature peaks in the data. Table 1 contains signature peaks for at least some of the phases that may be present in glass-ceramics including jeffvenite. The PDF number for each phase is typed in the "PDF Recall" column. The location of the PDF Recall column in the Phases window of MDI Jade is shown in Figure 14.

[0228] [Table 1]

[0229] For some phases, multiple solid solutions are possible. To make the card data match the sample data, the lattice parameters can be estimated. To estimate the lattice parameters, select the phase name in the Phases tab and select the ascending size arrow to the right of the main display. The location of the arrow is shown in Figure 15. The left and right mouse buttons may be used to raise and lower the lattice limits, respectively.

[0230] The phases listed in Table 1 will be found in glass-ceramic samples containing jeffvenite. If there are unidentified peaks in the data, the glass-ceramic composition and peak positions can be used to search the PDF-4 database. After identifying all phases and adjusting the lattice to match the sample data, use the "Assign Phases" function in the "Peaks" tab. The software will list the peaks and assign a phase to each peak. Some peaks may not have an assigned phase. This is indicated by peak number 1 in the list of peaks shown in Figure 16. If a peak does not contain an assigned phase, it is evaluated to determine whether it is a real peak or an artifact from either the instrument or the peak search algorithm. If the peak is a real peak, the PDF-4 database is manually searched to match the missing peak to the sample chemistry. Although the automated search query program is robust, the high degree of solid solution in some glass-ceramic articles can be problematic for the automated query program. Therefore, the operator may have to take the steps described above.

[0231] Using Topas, perform a Rietveld refinement to determine the lattice parameters and cell volume. Open the file "Jeffbenite with hkl phase and ZrO2.pro" in Topas. Run an initial refinement by clicking the red run arrow as shown in Figure 17. When the refinement has converged, hold the parameters. Next, bring the scan data from the X-ray diffractometer into Topas by clicking on the file name at the top of the file tree in the left hand window, navigating to the folder the data belongs to, selecting "Replace Scan Data", double clicking on the file containing the data, and loading the data. Figure 18 shows the location of "Replace Scan Data" in Topas. The file tree under Scan can be expanded so that all of the phases are visible. The model is set up to show the phases present in the current sample. This is done by clicking on the phase in the file tree and then checking or unchecking the "Use Phase" box in the structure window. Check the box if the phase is present and uncheck the box if the phase is not present. The location of the "Use Phase" box is shown in Figure 19. If there is no structure in the database that matches the experimental Jeffbenite, the Jeffbenite HKL phase is used in this step. The lattice parameters and cell volumes in the Jeffbenite HKL phase are the best match and are used to characterize the Jeffbenite in the sample.

[0232] Once the structure and all of the phases have been correctly identified for the sample, click the red run arrow and let Topas run the refinement until it converges on a solution. After the solution has converged, analyze the RwP value, Difference Plot, and Modeled Phase Data. The RwP value, Difference Plot, and Modeled Phase Data are shown in Figure 20. The RwP value in the top right window should be less than 5. In the Difference Plot, the curve between the experimental data and the modeled data (inside the ellipse) and the bar pattern of the phases are shown. If there is a peak in the difference curve, a phase is likely missing. If a phase is missing, repeat the phase identification step of the analysis. Analyze the Modeled Phase Data to determine if each phase is likely to be plausible. A plausible looking phase is one that is below the background, has no negative data points, and has a peak width that matches the experimental data. If the modeled phase data does not look plausible, then the model is likely to remain in a local minimum. If the model remains in a local minimum, restart the Rietveld refinement in Topas. If the RwP values, Difference Plot, and Modeled Phase Data are acceptable, then the lattice limits and cell volumes of the jeffvenite are accurate, the lattice limits and cell volumes of the sample are recorded.

[0233] In embodiments, the glass-ceramic article may have lattice parameters corresponding to jeffvenite and indicative of the presence of a jeffvenite crystalline phase in the glass-ceramic article. For example, in embodiments, the glass-ceramic article may have an "a" lattice parameter of 6.5 Å or more and 6.7 Å or less, or even 6.6 Å or more and 6.7 Å or less. In embodiments, the glass-ceramic article may have a "c" lattice parameter of 18.0 Å or more and 18.5 Å or less, 18.1 Å or more and 18.5 Å or less, 18.2 Å or more and 18.5 Å or less, 18.0 Å or more and 18.4 Å or less, 18.1 Å or more and 18.4 Å or less, or even 18.2 Å or more and 18.4 Å or less. In embodiments, the glass-ceramic article may have a "c" lattice parameter of 775 Å or more and 775 Å or more and 775 Å or more. 3More than or equal to 825Å 3 Below, 775Å 3 More than 810Å 3 Below, 790 Å 3 More than or equal to 825Å 3 Below, or even 790 Å 3 More than 810Å 3 In embodiments, the glass-ceramic article may have a peak position of 2.55 Å or more and 2.75 Å or less, 2.55 Å or more and 2.70 Å or less, 2.60 Å or more and 2.75 Å or less, 2.60 Å or more and 2.70 Å or more, 2.65 Å or more and 2.75 Å or less, or even 2.65 Å or more and 2.70 Å or less.

[0234] In embodiments, the glass-ceramic article may have an X-ray diffraction (XRD) spectrum corresponding to jeffvenite and indicating that jeffvenite crystalline phase is present in the glass-ceramic article. For example, in embodiments, the glass-ceramic article may have an XRD spectrum including a first peak between 2θ angles of 30° and 32°, a second peak between 2θ angles of 33° and 35°, a third peak between 2θ angles of 40° and 42°, and a fourth and fifth peak between 2θ angles of 55° and 58°, where the first, second, third, fourth, and fifth peaks correspond to jeffvenite. EXAMPLES

[0235] So that the various embodiments may be more readily understood, reference is made to the following examples, which are intended to illustrate various embodiments of the glass-ceramics described herein.

[0236] Table 2 shows exemplary precursor glass compositions AA-DH (mol %).

[0237] [Table 2-1]

[0238] [Table 2-2]

[0239]

Table 2-3

[0240]

Table 2-4

[0241]

Table 2-5

[0242]

Table 2-6

[0243]

Table 2-7

[0244]

Table 2-8

[0245]

Table 2-9

[0246]

Table 2-10

[0247]

Table 2-11

[0248]

Table 2-12

[0249] [Table 2-13]

[0250] Individual samples were formed by melting batches of the components to form a precursor glass having the composition indicated. The molten precursor glass was then poured into a steel mold and cooled to form a puck. The precursor glass puck was cut and then heat treated to form a glass ceramic. The glass ceramic samples were approximately 1 cm thick (unless otherwise noted).

[0251] The properties of the glass-ceramics were determined, including the crystalline phase, the appearance of the samples, the volume percent loss upon crystallization of the samples (i.e., shrinkage), the density of the precursor glass, the density of the glass-ceramic (GC), the percent increase in density, the elastic modulus, the shear modulus, the Poisson's ratio, the fracture toughness, and the Vickers hardness. The crystalline phase of the glass-ceramics was determined by the "Jeff-Venite characterization method" described above. The ceramming schedules to obtain the glass-ceramics GC1-GC97 and the respective properties of the glass-ceramics are shown in Tables 3-6.

[0252] When describing the appearance of the samples, the term "white" refers to a glass-ceramic that is white and opaque. The term "opalescent" refers to a glass-ceramic that is white and somewhat translucent. The term "transparent opalescent" refers to a glass-ceramic that is white but more translucent. In addition, some samples listed in Tables 3-6 were transparent, such as glass-ceramics GC22 and GC23 formed from batch compositions CX and CY, as shown in FIG. 30.

[0253] Tables 3-6 include several samples of glass-ceramics that contain jeffvenite. Tables 3-6 also include comparative examples in which the crystalline phase does not contain jeffvenite. For example, several compositions in Tables 3-6 (i.e., batch compositions AE, BI, BN, etc.) contain ZrO2 as a crystalline phase and jeffvenite is not present.

[0254]

Table 3-1

[0255]

Table 3-2

[0256]

Table 3-3

[0257]

Table 3-4

[0258]

Table 3-5

[0259]

Table 4-1

[0260]

Table 4-2

[0261]

Table 5-1

[0262]

Table 5-2

[0263]

Table 5-3

[0264] [Table 6-1]

[0265] [Table 6-2]

[0266] [Table 6-3]

[0267] [Table 6-4]

[0268] [Table 6-5]

[0269] [Table 6-6]

[0270] [Table 6-7]

[0271] [Table 6-8]

[0272] The lattice parameters of the glass-ceramics formed from the precursor glass compositions were determined by the "Jeff Benite Characterization Method" described above. The batch compositions, ceramming schedules, corresponding glass-ceramics, and lattice parameters are given in Table 7.

[0273] [Table 7]

[0274] The XRD spectra of the glass ceramics were obtained according to the "Jeff Benite Characterization Method" described above. XRD spectra of several glass-ceramic articles are included in the figures. The XRD spectrum of glass ceramic GC19 of Table 7 is shown in FIG. 21. The XRD spectrum of glass ceramic GC2 of Table 7 is shown in FIG. 22. The XRD spectrum of the glass ceramic formed by heat treating batch composition AB as shown in Table 7 is shown in FIG. 23. The XRD spectrum of glass ceramic GC71 of Table 7 is shown in FIG. 24. The XRD spectrum of glass ceramic GC20 of Table 7 is shown in FIG. 25. The XRD spectrum of glass ceramic GC21 of Table 7 is shown in FIG. 26. The XRD spectrum of glass ceramic GC24 of Table 7 is shown in FIG. 27.

[0275] The XRD spectrum of glass ceramic GC25 from Table 3 is shown in Figure 28. The XRD spectrum of glass ceramic GC26 from Table 3 is shown in Figure 29. Both glass ceramics GC25 and GC26 from Table 3 contain P2O5, which may improve diffusivity during the ion exchange process. The XRD spectra of glass ceramics GC25 and GC26 from Table 3 demonstrate that jeffvenite may form in glass ceramic articles containing P2O5.

[0276] Figure 3 shows the microstructure of glass ceramic GC53. Figure 4 shows the microstructure of glass ceramic GC4. Figure 3 also shows ZrO2 crystals (lighter colored areas) in the glass ceramic microstructure.

[0277] Samples of the glass-ceramic composition of batch composition AB were analyzed by high temperature X-ray diffraction (XRD). The samples were held for 1 hour at each of the following temperatures: 800°C, 825°C, 850°C, 875°C, 900°C, 925°C, 950°C, 975°C, and 1000°C. XRD spectra of the samples were obtained for the last 15 minutes of the period the samples were held at the particular temperatures. The XRD spectra are shown in FIG. 5. The high temperature XRD analysis indicates the range of stability of the various crystalline phases in the samples. As shown in FIG. 5, the samples contained a crystalline phase having a jeffvenite crystalline structure and a tetragonal ZrO2 crystalline phase.

[0278] The surface of the glass ceramic GC53 was observed by scanning electron microscope (SEM). The sample appeared translucent. To enable imaging by SEM, the surface of the sample was etched in 0.5% HF for 10 seconds. The conductive carbon coating on the sample was then evaporated to reduce charging. SEM images were taken of the surface of the sample using a Hitachi SU70 5 kV scanning electron microscope. The SEM images were obtained at magnifications from 5K to 150K. Figures 6A-6F show the surface of the sample. The magnification of the SEM micrographs increases from Figure 6A to Figure 6F. The grain size of the crystals in the sample was determined to be about 30 nm.

[0279] Referring now to Figure 7, a sample of the precursor glass composition of batch composition AP was heat treated at 780°C for 4 hours and 850°C for 4 hours to form a glass-ceramic. The resulting glass-ceramic was then analyzed by X-ray diffraction to obtain the diffraction pattern shown in Figure 7. The X-ray diffraction pattern shown in Figure 7 indicates that a composition in which a portion of the MgO is replaced with ZnO (in this case, 21.5% of the MgO is replaced with ZnO) can still result in the formation of a crystalline phase having a jeffvenite crystal structure upon heat treatment without the formation of other crystalline phases.

[0280] A sample having a thickness of 0.6 mm formed from the composition of batch composition AA was heat treated at 725° C. for 4 hours and 850° C. for 4 hours to form a glass ceramic. A sample having a thickness of 0.6 mm formed from the composition of batch composition AA was heat treated at 775° C. for 4 hours and 850° C. for 4 hours to form a glass ceramic. The glass ceramic samples were then ion-exchanged in a bath of 100 wt. % KNO3 for 1 hour, 2 hours, 4 hours, 8 hours, 16 hours, and 32 hours. The samples were then analyzed to determine the maximum surface compressive stress and maximum central tension as a function of ion-exchange time. The results are reported in Table 8.

[0281] [Table 8]

[0282] As shown in Table 8, with different ion exchange times, a maximum central tensile stress of up to 187.08 MPa and a maximum surface compressive stress of 690.57 MPa were achieved, indicating that the stress profile of the glass-ceramic can be tailored to meet different performance criteria.

[0283] The transmittance of samples of glass-ceramic compositions of batch composition AA cerammed at 725° C. for 4 hours and 850° C. for 4 hours was measured using the following procedure. Transmittance measurements were performed on a Lambda 950 UV-Vis-NIR Spectrophotometer manufactured by PerkinElmer Inc. (Waltham, Massachusetts, USA). In this example, the spectrophotometer used the following instrument settings: 150 mm integrating sphere; 2 nm data interval; detector switching (InGaAs to PMT) at 860 nm; lamp change at 340 nm; tungsten-halogen light source; InGaAs spectral bandwidth at servo; InGaAs gain of 15; InGaAs averaging time of 0.4 seconds; PMT spectral bandwidth of 3.5 nm; PMT averaging time of 0.2 seconds; and dual beam mode. For total transmittance (Total Tx), the sample was fixed at the entry point of the integrating sphere. For diffuse transmittance (Diffuse Tx), the Spectralon reference reflectance disc above the exit port of the sphere was removed to allow the on-axis light to exit the sphere and enter the light trap. To determine the efficiency of the light trap, a zero offset measurement of the diffuse portion was made without a sample. To correct the diffuse transmittance measurements, the zero offset contribution was calculated using the formula: Diffuse Tx = Diffuse 測定値 -(zero offset * The scattering ratio was measured for all wavelengths as (%Diffuse Tx / %Total Tx). The axial transmission was also measured. The axial transmission measurement was performed using on-axis light leaking out of the integrating sphere through the exit port. The total transmission of the glass-ceramic of Example A is shown in FIG. 10. The diffuse transmission of the glass-ceramic is shown in FIG. 11. The axial transmission of the glass-ceramic is shown in FIG. 12 and the scattering ratio of the glass-ceramic is shown in FIG. 13.

[0284] Using the procedure described above, the transmittance of five glass-ceramic articles was measured. The batch compositions, ceramming schedules, corresponding glass-ceramics, and thicknesses are listed in Table 9.

[0285] [Table 9]

[0286] The total transmittance for each of the glass-ceramics in Table 9 is shown in FIG. 31. The diffuse transmittance for each of the glass-ceramics in Table 9 is shown in FIG. 32. The scattering ratio for each of the glass-ceramics in Table 9 is shown in FIG. 33. The scattering ratios given in FIG. 33 are calculated according to the following formula: Scattering Ratio %=(%Diffuse Tx / %Total Tx). * Calculations were done using 100.

[0287] The following procedure was used to determine the color coordinates of each of the glass-ceramics listed in Table 9. Color measurements were made with a Lambda 950 UV / Vis Spectrophotometer manufactured by PerkinElmer Inc. (Weltham, Massachusetts, USA) as described above. Color coordinates were generally calculated using a weighting and summation of the spectral transmittance of the object, the spectral function of the "standard observer" of the human eye, and the power spectral distribution of the light source. Color coordinates for each sample were calculated from transmittance data obtained using three light sources: Standard Illuminant D65, Standard Illuminant A, and Standard Illuminant F2. Measurements were made using observer angles of 2° and 10°, and used a wavelength range of 770 nm to 380 nm (2 nm intervals). A first set of color coordinates was calculated using the total transmittance data from each of the glass-ceramic articles listed in Table 9, and a second set of color coordinates was calculated using the diffuse transmittance data from each of the glass-ceramic articles listed in Table 9. Color measurements made using total transmittance are included in Table 10 below. Color measurements made using diffuse transmittance are included below in Table 11. Tables 10 and 11 are based on the CIE L * A * B * It contains color space data, as well as CIE Yxy color space data.

[0288] [Table 10]

[0289] [Table 11]

[0290] As part of exploring the presently disclosed technology of precursor glass compositions and glass ceramics formed therefrom, in addition to the above examples and disclosures relating to glass ceramics containing jeffvenite, the following table provides additional compositions melted by applicant as described herein, which correspond to the information disclosed herein, as well as other samples disclosed and further described herein. The additional compositions, expressed in mole percent on an oxide basis, are listed in Table 12.

[0291] [Table 12-01]

[0292] [Table 12-02]

[0293] [Table 12-03]

[0294] [Table 12-04]

[0295] [Table 12-05]

[0296] [Table 12-06]

[0297]

Table 12-07

[0298]

Table 12-08

[0299]

Table 12-09

[0300]

Table 12-10

[0301]

Table 12-11

[0302]

Table 12-12

[0303]

Table 12-13

[0304]

Table 12-14

[0305]

Table 12-15

[0306]

Table 12-16

[0307]

Table 12-17

[0308]

Table 12-18

[0309]

Table 12-19

[0310]

Table 12-20

[0311]

Table 12-21

[0312]

Table 12-22

[0313]

Table 12-23

[0314]

Table 12-24

[0315]

Table 12-25

[0316]

Table 12-26

[0317]

Table 12-27

[0318]

Table 12-28

[0319]

Table 12-29

[0320]

Table 12-30

[0321]

Table 12-31

[0322]

Table 12-32

[0323]

Table 12-33

[0324]

Table 12-34

[0325]

Table 12-35

[0326]

Table 12-36

[0327]

Table 12-37

[0328] [Table 12-38]

[0329] [Table 12-39]

[0330] [Table 12-40]

[0331] [Table 12-41]

[0332] [Table 12-42]

[0333] [Table 12-43]

[0334] [Table 12-44]

[0335] It will be apparent to those skilled in the art that various modifications and variations may be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Therefore, it is intended that this specification cover modifications and variations of the various embodiments described herein, provided such modifications and variations come within the scope of the appended claims and their equivalents.

[0336] Preferred embodiments of the present invention will be described below in detail.

[0337] EMBODIMENT 1 Glass-ceramic containing jeffvenite.

[0338] EMBODIMENT 2 In the case of goods, Surface, and A body inside the surface, the body being made from the glass ceramic according to embodiment 1. An article equipped with the above.

[0339] EMBODIMENT 3 3. The article of claim 2, wherein the surface is a first surface, the article further having a second surface facing away from the first surface, and the body is positioned between the first surface and the second surface such that the article is a sheet.

[0340] EMBODIMENT 4 1. A method of producing a material, comprising: growing jeffvenite at a pressure of less than 10 GPa; The method includes:

[0341] EMBODIMENT 5 5. The method of embodiment 4, wherein the growing step is performed at a temperature of less than 1400K.

[0342] EMBODIMENT 6 5. The method of claim 4, wherein the jeffvenite is grown as a crystalline phase within a glass to form a glass-ceramic.

[0343] EMBODIMENT 7 In the glass-ceramic article, Front page, a second surface opposite said first surface; a periphery defining a shape of the glass-ceramic article; and a phase assemblage comprising one or more crystalline phases and a glassy phase, the one or more crystalline phases comprising a crystalline phase having a jeffvenite crystal structure; 1. A glass-ceramic article comprising:

[0344] EMBODIMENT 8 8. The glass-ceramic article of embodiment 7, wherein the crystalline phase having the jeffvenite crystal structure is a predominant crystalline phase.

[0345] EMBODIMENT 9 9. The glass-ceramic article of claim 7 or 8, wherein the phase assemblage comprises 25% by weight or more of the one or more crystalline phases and 75% by weight or less of the glassy phase.

[0346] EMBODIMENT 10 10. The glass-ceramic article of any one of claims 7 to 9, wherein at least some grains of the crystalline phase having the jeffvenite crystal structure have a maximum dimension of 20 nm or more and 100 nm or less.

[0347] EMBODIMENT 11 11. The glass-ceramic article of any one of claims 7 to 10, wherein the glass-ceramic article is substantially free of lithium.

[0348] EMBODIMENT 12 The crystalline phase having the jeffvenite crystal structure has the formula: (Mg,R 2+ ) 3+x (Zr,R 4+ ) x Al 2-2x SiO 12 wherein R 2+ is a divalent metal cation, and R 4+ is a tetravalent metal cation and x is 0 or more and 1 or less.

[0349] EMBODIMENT 13 R 2+ But, Ca 2+ , Mn 2+ , Fe 2+ and R is one or more divalent metal cations selected from 4+ But, Ti 4+ , Sn 4+ , Hf 4+13. The glass-ceramic article of embodiment 12, wherein the one or more tetravalent metal cations are selected from:

[0350] EMBODIMENT 14 14. The glass-ceramic article of any one of claims 7 to 13, wherein the glass-ceramic article has an average transmittance of at least 75% for light in the wavelength range of 400 nm to 800 nm at an article thickness of 0.6 mm.

[0351] EMBODIMENT 15 In the glass-ceramic article, in mole percent (mol%) on an oxide basis: 35 mol% or more and 65 mol% or less of SiO2; 5 mol% or more and 20 mol% or less of Al2O3, 7 mol % or more and 65 mol % or less of MgO; 0 mol% to 7 mol% ZrO2; 0 mol% to 15 mol% Na2O, 0 mol% to 15 mol% K2O, FeO of 0 mol% or more and 9 mol% or less, 0 mol% to 10 mol% MnO2, and 0 mol % or more and 15 mol % or less of ZnO; Including, 1. A glass-ceramic article, wherein the glass-ceramic comprises a phase assemblage comprising one or more crystalline phases and a glassy phase, the one or more crystalline phases comprising a crystalline phase having a jeffvenite crystal structure.

[0352] EMBODIMENT 16 16. The glass-ceramic article of embodiment 15, further comprising up to 3 mol % LiO2.

[0353] EMBODIMENT 17 16. The glass-ceramic article of claim 15, wherein the glass-ceramic article is substantially free of LiO2.

[0354] EMBODIMENT 18 18. The glass-ceramic article of any one of claims 15 to 17, wherein the glass-ceramic article comprises from 1.5 mol% to 3 mol% ZrO2.

[0355] EMBODIMENT 19 19. The glass-ceramic article of any one of claims 15 to 18, wherein the glass-ceramic article comprises from greater than 0 mol% to less than or equal to 12 mol% HfO2, and the sum of ZrO2 and HfO2 is greater than 1 mol%.

[0356] EMBODIMENT 20 20. The glass-ceramic article of any one of claims 15 to 19, wherein the glass-ceramic article comprises from greater than 0 mol% to less than or equal to 15 mol% CaO.

[0357] EMBODIMENT 21 21. The glass-ceramic article of any one of claims 15 to 20, wherein the glass-ceramic article comprises from greater than 0 mol% to less than or equal to 4 mol% P2O5.

[0358] EMBODIMENT 22 22. The glass-ceramic article of any one of claims 15 to 21, wherein the glass-ceramic article comprises from greater than 0 mol% to less than or equal to 7 mol% La2O3.

[0359] EMBODIMENT 23 23. The glass-ceramic article of any one of embodiments 15 to 22, wherein Na2O(mol%)+K2O(mol%) is from 2 mol% or more to 15 mol% or less.

[0360] EMBODIMENT 24 24. The glass-ceramic article of any one of claims 15 to 23, wherein Na2O(mol%) / (Na2O(mol%)+K2O(mol%)) is 0.2 or greater.

[0361] EMBODIMENT 25 25. The glass-ceramic article of any one of embodiments 15 to 24, further comprising greater than or equal to 0.3 mol % and less than or equal to 7 mol % TiO2.

[0362] EMBODIMENT 26 26. The glass-ceramic article of any one of embodiments 15 to 25, wherein ZrO2 (mol%) + TiO2 (mol%) is 2 mol% or more.

[0363] EMBODIMENT 27 27. The glass-ceramic article of any one of embodiments 15 to 26, wherein ZrO2(mol%) / (ZrO2(mol%)+TiO2(mol%)) is 0.3 or greater.

[0364] EMBODIMENT 28 28. The glass-ceramic article of any one of embodiments 15 to 27, comprising from ≧1 mol % to ≦12 mol % ZnO.

[0365] EMBODIMENT 29 29. The glass-ceramic article of any one of embodiments 15 to 28, further comprising from ≧1 mol % to ≦8 mol % BaO.

[0366] EMBODIMENT 30 30. The glass-ceramic article of any one of embodiments 15 to 29, further comprising from 0.2 mol % to 1.7 mol % of at least one of CaO and SrO.

[0367] EMBODIMENT 31 1. A method of making a glass-ceramic article, comprising: heat treating a precursor glass comprising SiO, AlO, and MgO to nucleate one or more crystalline phases in the precursor glass, the one or more crystalline phases comprising a crystalline phase having a jeffvenite crystal structure; and growing said one or more crystalline phases within a glassy phase; The method comprising:

[0368] EMBODIMENT 32 The heat treatment step comprises: Heating the precursor glass in an environment of 700° C. or more and 950° C. or less; and maintaining the precursor glass in the environment for a first period of time, the first period being from 0.25 hours to 6 hours; 32. A method for making the glass-ceramic article of embodiment 31, comprising:

[0369] EMBODIMENT 33 The heat treatment step comprises: Heating the precursor glass in an environment of 750° C. or more and 950° C. or less; and maintaining the precursor glass in the environment for a second period of time, the second period being from 0.25 hours to 6 hours; 33. A method for making the glass-ceramic article of embodiment 32, comprising:

[0370] EMBODIMENT 34 In the glass ceramic sheet, a first major surface and a second major surface facing away from the first major surface, an edge forming an outer periphery of the first and second major surfaces and extending between the first and second major surfaces, and a body between the first and second major surfaces and the edge, the body being made from a glass-ceramic including a crystalline phase having a jeffvenite crystal structure; the thickness of the sheet is defined as the distance between the first and second major surfaces, the width of the sheet is defined as the distance between the edges along the first major surface perpendicular to the thickness, and the length of the sheet is defined as the distance between the edges along the first major surface perpendicular to both the width and the thickness; said width being greater than or equal to said thickness; The glass-ceramic sheet, wherein the length is greater than or equal to the width.

[0371] EMBODIMENT 35 35. The glass-ceramic sheet of embodiment 34, wherein grains of a crystalline phase having a jeffvenite crystal structure are uniformly distributed throughout the glass-ceramic body.

[0372] EMBODIMENT 36 36. The glass-ceramic sheet of claim 34 or 35, wherein grains of the crystalline phase having the jeffvenite crystal structure are randomly oriented within the body glass-ceramic.

[0373] EMBODIMENT 37 The grains of the crystalline phase having the jeffvenite crystal structure are within the glass-ceramic body and have a fracture toughness of 0.75 MPa m 1 / 2 37. The glass-ceramic sheet according to any one of embodiments 34 to 36, wherein the glass-ceramic sheets overlap and interlock with each other to such an extent that ... interdigitate with each other to such an extent that the glass-ceramic sheets interdigitate with each other to such an extent that the glass-ceramic sheets interdigitate with each other to such an extent that the glass-ceramic sheets interdigit

[0374] EMBODIMENT 38 38. The glass-ceramic sheet of any one of claims 34 to 37, wherein the glass-ceramic has isotropic material properties.

[0375] EMBODIMENT 39 39. The glass-ceramic sheet according to any one of claims 34 to 38, wherein the thickness is 200 μm or more and 5 mm or less, and the length and width are both greater than 5 mm.

[0376] EMBODIMENT 40 1. A method for producing a glass ceramic, comprising: heat treating a precursor glass including nucleation sites to grow particles of a crystalline phase having a javenite crystal structure from the nucleation sites in the precursor glass to form a glass ceramic including a crystalline phase having a javenite crystal structure and residual glass; and growing grains of a crystalline phase having a jaeffvenite crystal structure during said heat treatment such that at least some of said grains have a dimension of 20 nm or greater; The method comprising:

[0377] EMBODIMENT 41 41. The method of embodiment 40, wherein the growing step is carried out at atmospheric pressure.

[0378] EMBODIMENT 42 42. The method of claim 40 or 41, wherein after the growing step, at least some of the particles of the crystalline phase having the jeffvenite crystal structure have dimensions of 5 μm or less.

[0379] EMBODIMENT 43 In the glass-ceramic article, Crystals of pyrope-almandine garnet stoichiometry with a tetragonal structure, and an amorphous glass that surrounds and encapsulates the crystals such that the crystals and glass together form the glass-ceramic of the glass-ceramic article; 1. A glass-ceramic article comprising:

[0380] EMBODIMENT 44 44. The glass-ceramic article of claim 43, wherein the tetragonal structure falls within the I-42d space group.

[0381] EMBODIMENT 45 In the glass-ceramic article, "a" lattice parameter greater than or equal to 6.5 Å and less than or equal to 6.7 Å, a "c" lattice parameter greater than or equal to 18.0 Å and less than or equal to 18.5 Å; and a first peak between 2θ angles of 30° and 32°; a second peak between 2θ angles of 33° and 35°; a third peak between 2θ angles of 40° and 42°; a fourth peak and a fifth peak between 2θ angles of 55° and 58°; An X-ray diffraction spectrum having an X-ray diffraction spectrum, wherein the first, second, third, fourth, and fifth peaks correspond to jeffvenite; 1. A glass-ceramic article comprising: [Explanation of symbols]

[0382] 100 Consumer Electronics 102 Case 104 Front 106 Back 108 Side 110 Display 112 Cover board 200, 810 Glass ceramic articles 201 Main unit 202 Front page 204 Second page 206 Edge Face 812 Glass phase 814, 816 crystal phase

Claims

1. Glass-ceramic containing jeffvenite.

2. In the case of goods, Surface, and A body inside the surface, the body being made from the glass ceramic according to embodiment 1. An article equipped with the above.

3. 3. The article of claim 2, wherein the surface is a first surface, the article further having a second surface facing away from the first surface, and the body is positioned between the first surface and the second surface such that the article is a sheet.

4. 1. A method of producing a material, comprising: growing jeffvenite at a pressure of less than 10 GPa; The method includes:

5. The method of claim 4 , wherein the growing step is performed at a temperature below 1400K.

6. The method of claim 4 , wherein the jeffvenite is grown as a crystalline phase within the glass to form a glass-ceramic.